Assessment criteria indicative of deception (ACID): Replication and gender differences - Suckle-Nelson, Jessica A.; Colwell, Kevin; Hiscock-Anisman, Cheryl; Florence, Samantha; Youschak, Kimberly E.; Duarte, Arianne (The Open Criminology Journal, 2010)
Keywords: dept.psy

Normal Probability Distributions - Hauselt Jr, William J (Statistics for Social Science | Top Hat, 2016)
Keywords: dept.psy

Turning molehills into mountains: Sleepiness increases workplace interpretive bias - Barber, Larissa K.; Budnick, Christopher J. (Journal of Organizational Behavior, 2015)
Three studies draw from evolutionary theory to assess whether sleepiness increases interpretive biases in workplace social judgments. Study 1 established a relationship between sleepiness and interpretive bias using ambiguous interpersonal scenarios from a measure commonly used in personnel selection (N = 148). Study 2 explored the boundary conditions of the sleepiness–interpretive bias link via an experimental online field survey of U.S. adults (N = 433). Sleepiness increased interpretive bias when social threats were clearly present (unfair workplace) but did not affect bias in the absence of threat (fair workplace). Study 3 replicated and extended findings from the previous two studies using objective measures of sleep loss and a quasi-experimental manipulation of minor sleep loss (N = 175). Negative affect, ego depletion, or personality variables did not influence the observed relationships. Overall, results suggest that a self-protection/evolutionary perspective best explains the effects of sleepiness on workplace interpretive biases. These studies advance the current research on sleep in organizations by adding a cognitive “threat interpretation” bias approach to past work examining the emotional reaction/behavioral side of sleep disruption. Interpretive biases due to sleepiness may have significant implications for employee health and counterproductive behavior. Copyright © 2015 John Wiley & Sons, Ltd.
Keywords: Conditional Reasoning Test of Aggression; dept.psy; fairness; interpretive bias; sleep; work perceptions

Behind sleepy eyes: Implications of sleep loss for organizations and employees - Budnick, Christopher J.; Barber, Larissa K. (Translational Issues in Psychological Science, 2015)
Sleep loss and daytime sleepiness are common experiences for employees across many occupations. Although researchers commonly focus on the detrimental effects of sleep issues for attention and vigilance during task performance, we review research that examines how sleep issues influence interpretations of, and interactions in, the work environment. This review begins by differentiating between sleep loss and sleepiness. We then highlight how sleep issues can negatively bias the interpretation of environmental information and result in aggressive responding. We also examine how sleep issues impair self-regulatory ability and contribute to workplace deviance. After each section, we discuss the implications of these findings for the work environment. A closer examination of sleep’s influence on workplace interactions can spur a beneficial discussion for researchers across a variety of disciplines and employees across all organizational levels. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: Aggressive Behavior; Employee Productivity; Health; Occupations; Organizations; Personnel; Self-Control; Sleep Deprivation; Sleepiness; Stress; Working Conditions; dept.psy

Longitudinal Effects of Early Reading Interventions on Normed, Standardized Reading Outcome Measures. - Carroll, Deborah A. (2019)
Keywords: dept.psy; faculty_collection; sabbatical_report

Learning and Behavior - Mazur, James E. (Pearson, 2013)
Keywords: Learning, Psychology of; Conditioned response; Behavior modification; Psychology, Comparative; dept.psy

Preparing Children for Reading Success: Hands-On Activities for Librarians, Educators, and Caregivers - Irwin, Julia; Moore, Dina (Rowman & Littlefield Publishers, 2014)
Designed to familiarize anyone who reads to young children with the essentials of promoting early and emerging literacy. Irwin and Moore share activities that can be used to foster this critical skill development, and have linked these activities to popular children's books.--
Keywords: Books and reading; Creative activities and seat work; Reading; Literacy; Children; dept.psy; faculty_collection

Change in suspect's memory as a result of deception - Colwell, K.; Hiscock-Anisman, C.; Corbett, L.; Memon, A.; Hauselt, W.J.; Bonilla, Y. (American Journal of Forensic Psychology, 2011)
One hundred and eight participants either stole or replaced a stolen exam key from a professor's office. Half of the participants were instructed to respond honestly and to help with an investigation; the other half were instructed to distort their statement so they were not implicated. Participants did not know whether they would be asked to lie or report honestly during their time in the professor's office. After completing the task, participants again met with a research assistant, who instructed them whether to lie or respond honestly at a one-week follow-up. After the interview, participants completed a Likert-type post-event questionnaire. Deceivers reported significantly more anxiety and motivation not to get caught while in the office, even though there were no differences in the instructions given to the two groups until after participants left the office. Therefore, the act of deception changed their memory for their time in the office. This is important theoretically because it suggests that forming a lie script could be akin to other memories for counterfactual thinking. Practically, it is important to note that a deceptive perpetrator or detainee may never be able to actually provide an accurate account. Copyright 2011 American Journal of Forensic Psychology.
Keywords: anxiety; article; deception; dept.psy; female; follow up; honesty; human; human experiment; male; memory; motivation; normal human; offender; questionnaire; task performance; theft; thinking; ⛔ No DOI found

Forgiveness in Counseling: Caution, Definition, and Application - Affinito, M.G. (Before Forgiving: Cautionary Views of Forgiveness in Psychother., 2012)
This chapter highlights that forgiveness is a decision that clients should be helped to make and that advocacy has little place in the counseling session. It specifically confirms the value of forgiveness in the counseling setting and offers some guidelines for its effective application. There are at least three approaches to justice, altering in the extent to which they are proactive or reactive, past or future oriented, limited or general: (1) retributive justice, (2) restorative justice, and (3) pervasive justice. The pragmatic model needs an in-depth investigation of alternatives; their practical and moral costs and their benefits. It is concluded that there can be no relief unless the offender confesses and asks forgiveness, and argues that repentance is poor therapy and of questionable morality, because it leaves clients in a state of helpless dependence on the person or persons who offended them in the first place. © 2002 by Oxford University Press, Inc. All rights reserved.
Keywords: Caution; Counseling; Forgiveness; Justice; Pervasive justice; Pragmatic model; Restorative justice; Retributive justice; dept.psy

Neurobiological and behavioral studies of skilled and impaired word reading - Frost, S.J.; Sandak, R.; Mencl, W.E.; Landi, N.; Moore, D.; Porta, G.D.; Rueckl, J.G.; Katz, L.; Pugh, K.R. (Single-Word Read.: Behavioral and Biological Perspectives, 2012)
Keywords: dept.psy

Affective awareness in parenting of fathers with co-occurring substance abuse and intimate partner violence - Gilchrist, G.; Smith Stover, C.; Spink, A. (Advances in Dual Diagnosis, 2012)
Few studies have examined the parenting of fathers with cooccurring substance abuse (SA) and intimate partner violence (IPV) problems. None have specifically interviewed men with these cooccurring issues using qualitative methods about their reflective functioning in relation to their children. This paper aims to provide evidence of the reflective capacity of fathers with cooccurring SA and IPV. To assess this, men were asked to describe examples of negative emotions they experienced as parents and how they perceived their children responded to those emotions. In total, 40 fathers with cooccurring SA and IPV were interviewed using the Revised Parent Development Interview. Interviews were coded for reflective functioning and for themes that emerged related to angry and guilty feelings these fathers experienced as parents. Overall, fathers in the sample had a very limited capacity to think about the thoughts and feelings of their children. The desire to spend more time with their child and an inability to provide financially were two common themes. Anger toward the child's mother for not providing adequate care and a focus on shielding the child from his anger were also reported frequently. Fathers did not report feelings of guilt related to their substance use or aggression in their relationships. This paper is one of the first to explore reflective functioning of fathers with cooccurring IPV and SA. These findings are discussed in relation to their implications for intervention with fathers with cooccurring SA and IPV issues. © 2012, Emerald Group Publishing Limited
Keywords: Domestic violence; Drug addiction; Fathers; Intimate partner violence; Men; Parenting; Substance abuse; United States of America; dept.psy

Using acid to improve credibility assessments with written and audio statements - Montalvo, L.; Hallinan, C.; Hiscock-Anisman, C.; Morrissey, D.; Bonilla, Y.; Colwell, K. (American Journal of Forensic Psychology, 2013)
Investigators are continually faced with the task of detecting deception. Assessment Criteria Indicative of Deception (ACID) is a system of interviewing and credibility assessment that maximizes verbal cues to detect deception, and teaches content analysis that highlights attempts to withhold, distort, or manipulate information. The ACID technique has been successful in discriminating honest from deceptive statements when credibility determinations are made either by statistical methods or trained raters. Unfortunately, the training has required several hours and application has required the time-consuming process of transcription. The current study demonstrates the utility of ACID following a brief training, and compares the credibility ratings made from analysis of transcripts to the credibility ratings made from the analysis of audio recordings. Twenty-nine university undergraduate and graduate students read or listened to a series of eight transcripts. Raters were provided with accounts before training and 4 accounts after training. Prior to training, raters performed at 55% accuracy. Following training, raters performed at 71% accuracy. Additionally, there was an untrained control group that performed at 53% accuracy. Of note, the post-training performance was identical for accounts presented in written and audio formats. In sum, the ACID technique was reliable, valid, easy to train, and showed that accurate decisions can be made from simple audio recordings. Copyright 2013 American Journal of Forensic Psychology,.
Keywords: accuracy; adult; article; assessment criteria indicative of deception; audiology; clinical assessment tool; clinical decision making; clinical education; content analysis; controlled study; deception; dept.psy; human; human experiment; meaningful use criteria; reliability; statistical analysis; validity; written language; ⛔ No DOI found

Screening for reading disability in university students with phonological processing and working memory tasks - Broggi, M., Jr.; Ready, R.E.; Moore, D.L. (Dyslexia, 2019)
Many students in higher education have undiagnosed reading disabilities (RDs), but there are few measures to screen for RD in this population. The aim of this study was to determine the ability of tasks that are sensitive to RDs—such as measures of phonemic awareness and working memory—to differentiate university students previously diagnosed with RDs from controls. Participants were university students with an RD (n = 26), a clinical control group diagnosed with attention-deficit/hyperactivity disorder (n = 24), and neurotypical controls (n = 44). Participants completed brief phonological processing and working memory tasks. The RD group scored significantly lower on all tasks than both control groups. The phonological processing tasks alone—without the working memory task—discriminated participants with RDs from controls with excellent sensitivity and specificity. A brief battery of phonemic tasks could be an effective screening instrument for persons with RDs on university campuses. © 2019 John Wiley & Sons, Ltd.
Keywords: Attention Deficit Disorder with Hyperactivity; Awareness; Dyslexia; Female; Humans; Learning Disorders; Male; Memory, Short-Term; Phonetics; Reading; Students; Task Performance and Analysis; Universities; Young Adult; attention deficit disorder; awareness; dept.psy; dyslexia; female; human; learning disorder; male; peer-reviewed; phonetics; phonological processing; psychology; reading; reading disability; screening test; short term memory; student; task performance; university; university students; working memory; young adult

Does the risk of sperm competition help explain cooperation between reproductive competitors? A study in the ocellated wrasse (Symphodus ocellatus). - Stiver, Kelly A; Alonzo, Suzanne H (The American naturalist, 2013)
Although cooperating individuals may gain benefits, they risk being cheated by their allies. Therefore, to understand the persistence of cooperation by mutual benefits, it is important to document both the potential benefits of cooperation and the risks of cheating. We experimentally examined evidence of cooperation in the ocellated wrasse (Symphodus ocellatus), a fish species with males that exercise three reproductive strategies: satellite and sneaker males attempt to parasitically spawn in the nests of nesting males. Nesting males have been hypothesized to tolerate satellites as a result of satellite aid in defense against sneaker males and help in courting females. Here, we provide evidence that cooperation between reproductive competitors may arise in response to sperm competition from other males. After we experimentally removed satellites, nesting males had more sneakers at their nest and experienced a higher rate of sneaking when they spawned (increased sperm competition risk). When we experimentally distracted nesting males to prevent their acting aggressively toward satellites, satellites spawned with females and ate eggs in the nest. Our results suggest that nesting males and satellites gain fitness benefits of reduced direct reproductive and sperm competition through cooperation. However, nesting males risk losing paternity, while satellites experience increased aggression and must invest in aggression themselves (i.e., they act aggressively toward sneakers).
Keywords: *Competitive Behavior/ph [Physiology]; *Cooperative Behavior; *Perciformes/ph [Physiology]; *Sexual Behavior, Animal/ph [Physiology]; *Spermatozoa/ph [Physiology]; Aggression; Alternative male tactics; Analysis of Variance; Animals; Competition; Competitive Behavior; Cooperation; Cooperative Behavior; Female; Fertility; Fertility/ph [Physiology]; Male; Models, Biological; Nesting Behavior; Nesting Behavior/ph [Physiology]; Perciformes; Sexual Behavior, Animal; Sneak-fertilization; Sperm competition; Spermatozoa; aggression; analysis of variance; animal; article; biological model; competitive behavior; cooperation; cooperative breeding; dept.psy; female; fertility; male; nesting; peer-reviewed; perciform; persistence; physiology; reproductive strategy; sexual behavior; sneak copulation; sperm competition; spermatozoon

Is women's participation in different types of yoga classes associated with different levels of body awareness and body satisfaction? - Delaney, Kelley; Anthis, Kristine (International Journal of Yoga Therapy, 2010)
Keywords: dept.psy

Integrating DSM-IV factors to predict violence in high-risk psychiatric patients - Lynch, Donna M.; Noel, Helen C. (Journal of Forensic Sciences, 2010)
This study incorporated Axis-II and Axis-IV factors in DSM-IV to test the relationship between predicted risk for violence assessed in the psychiatric emergency room and actual violence during hospitalization. Psychiatric nurses lack an objective instrument to use during the acute psychiatric assessment. The retrospective study comprised consecutive psychiatric admissions (n = 161) in one tertiary veterans' hospital. Statistical testing for the predictive power of risk factors, relationships between variables, and violent events included nonparametric tests, factor analysis, and logistic regression. Of the 32 patients who committed violence during hospitalization, 12 had committed violence in the psychiatric emergency room. Statistical significance was shown for violent incidents and dementia, court-ordered admission, mood disorder, and for three or more risk factors. The 13-item Risk of Violence Assessment (ROVA) scale suggests validity and sensitivity for rating DSM-IV factors and psychosocial stressors to predict risk for violence during hospitalization. Replication studies are recommended to strengthen validity of the ROVA scale.
Keywords: Adult; Aged; Aged, 80 and over; Aggression; Assault; Assessment; Commitment of Mentally Ill; Dementia; Diagnostic and Statistical Manual of Mental Disorders; Diagnostic and statistical manual of mental disorders (DSM-IV); Emergency Services, Psychiatric; Female; Forensic Psychiatry; Forensic science; Hospitals, Veterans; Humans; Instrument; Male; Mental Disorders; Middle Aged; New England; Psychiatric; Psychiatric Status Rating Scales; Reproducibility of Results; Retrospective Studies; Risk Assessment; Risk factors; Self-harm; Suicidal; United States; Violence; adult; aged; article; dementia; dept.psy; diagnostic and statistical manual of mental disorders; emergency health service; female; forensic psychiatry; human; male; mental disease; middle aged; psychological aspect; psychological rating scale; public hospital; reproducibility; retrospective study; risk assessment; violence

The role of conflict in continuity and change: life events associated with identity development in racially and ethnically diverse women - Anthis, Kristine (Identity, 2011)
In this archival study, life events were identified that served as precursors to identity transitions in 149 European American, African American, Mexican American, and Puerto Rican women. The data were collected during a period from the late 1970s to the early 1980s in the United States. Participants were interviewed and asked to describe events that had influenced their understanding of themselves. Events were coded into relational, career, education, personal, health-related, and miscellaneous categories. Results indicated that women were more likely to report life events regarding their relationships than events in other categories. A reexamination of the data revealed that that there were more similarities than differences among the racial and ethnic groups in terms of the life events described. Respondents were more likely to report continuity than change in their identities in response to life events serving as possible precursors to change. Results also revealed that when change did occur, it was associated with high levels of conflict particularly for the domains of relationships and educational achievement expectations. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy

Mindfulness and modification therapy for behavioral dysregulation: results from a pilot study targeting alcohol use and aggression in women - Wupperman, Peggilee; Marlatt, G. Alan; Cunningham, Amy; Bowen, Sarah; Berking, Matthias; Mulvihill-Rivera, Nicole; Easton, Caroline (Journal of Clinical Psychology, 2012)
Objectives: Increasing evidence suggests that deficits in mindfulness (awareness, attentiveness, and acceptance of the present moment) play a role in a range of disorders involving behavioral dysregulation. This paper adds to that literature by describing a transdiagnostic psychotherapy (Mindfulness & Modification Therapy; MMT) developed to target behavioral dysregulation. Design: An open-treatment pilot-trial investigated the feasibility, acceptability, and pre-post effects of MMT targeting women (N = 14) court-referred for alcohol abuse/dependence and aggression. Results: Pre-post comparisons revealed significant decreases in alcohol use, drug use, and aggression. In addition, the retention rate was 93%. Conclusion: Preliminary evidence suggests that MMT is a feasible and acceptable treatment that decreases dysregulated behaviors such as substance use and aggression, while also potentially increasing retention. (c) 2011 Wiley Periodicals, Inc. J Clin Psychol 67:117, 2011.
Keywords: Adult; Aggression; Alcoholism; Anger; Attention; Awareness; Behavior dysregulation; Cognitive Therapy; Domestic Violence; Emotion regulation; Emotions; Female; Humans; Intervention; Middle Aged; Mindfulness; Pilot Projects; Substance; Transdiagnostic; Treatment Outcome; Young Adult; adult; aggression; alcoholism; article; attention; awareness; cognitive therapy; dept.psy; domestic violence; emotion; female; human; legal aspect; methodology; middle aged; physiology; pilot study; psychological aspect; treatment outcome

Neuroendocrine profiles associated with discrete behavioural variation in Symphodus ocellatus, a species with male alternative reproductive tactics. - Nugent, Bridget M.; Stiver, Kelly A.; Alonzo, Suzanne H.; Hofmann, Hans A. (Molecular Ecology, 2016)
The molecular mechanisms underlying phenotypic plasticity are not well understood. Identifying mechanisms underlying alternative reproductive tactics (ARTs) in species for which the behavioural and fitness consequences of this variation are well characterized provides an opportunity to integrate evolutionary and mechanistic understanding of the maintenance of variation within populations. In the ocellated wrasse Symphodus ocellatus, the behavioural phenotypes of three distinct male morphs (sneakers, satellites and nesting males), which arise from a single genome, have been thoroughly characterized. To determine the neuroendocrine and genomic mechanisms associated with discrete phenotypic variation and ARTs in S. ocellatus in their natural environment, we constructed a whole-brain de novo transcriptome and compared global patterns of gene expression between sexes and male morphs. Next, we quantified circulating cortisol and 11-ketotestosterone (11-kt), mediators of male reproductive behaviours, as well as stress and gonadal steroid hormone receptor expression in the preoptic area, ventral subpallial division of the telencephalon and dorsolateral telencephalon, critical brain regions for social and reproductive behaviours. We found higher levels of 11-kt in nesting males and higher levels of cortisol in sneaker males relative to other male morphs and females. We also identified distinct patterns of brain region-specific hormone receptor expression between males such that most hormone receptors are more highly expressed in satellites and nesting males relative to sneakers and females. Our results establish the neuroendocrine and molecular mechanisms that underlie ARTs in the wild and provide a foundation for experimentally testing hypotheses about the relationship between neuromolecular processes and reproductive success. Copyright © 2016 John Wiley & Sons Ltd.
Keywords: *Neurosecretory Systems/ph [Physiology]; *Perciformes/ph [Physiology]; *Reproduction; *Sexual Behavior, Animal; 11-ketotestosterone; Animals; Brain; Brain/me [Metabolism]; Female; Hydrocortisone; Hydrocortisone/bl [Blood]; Male; Nesting Behavior; Neurosecretory Systems; Perciformes; Perciformes/ge [Genetics]; Phenotype; Reproduction; Sexual Behavior, Animal; Testosterone; Testosterone/aa [Analogs & Derivatives]; Testosterone/bl [Blood]; Transcriptome; alternative reproductive tactics; analogs and derivatives; animal; blood; brain; dept.psy; female; gene expression; genetics; hormones; hydrocortisone; male; metabolism; nesting; neurosecretion; peer-reviewed; phenotype; physiology; reproduction; sexual behavior; testosterone; transcriptome

Ocean acidification affects fish spawning but not paternity at CO2 seeps - Milazzo, Marco; Cattano, Carlo; Alonzo, Suzanne H; Foggo, Andrew; Gristina, Michele; Rodolfo-Metalpa, Riccardo; Sinopoli, Mauro; Spatafora, Davide; Stiver, Kelly A; Hall-Spencer, Jason M (Proceedings of the Royal Society B: Biological Sciences, 2016)
Fish exhibit impaired sensory function and altered behaviour at levels of ocean acidification expected to occur owing to anthropogenic carbon dioxide emissions during this century. We provide the first evidence of the effects of ocean acidification on reproductive behaviour of fish in the wild. Satellite and sneaker male ocellated wrasse (Symphodus ocellatus) compete to fertilize eggs guarded by dominant nesting males. Key mating behaviours such as dominant male courtship and nest defence did not differ between sites with ambient versus elevated CO2 concentrations. Dominant males did, however, experience significantly lower rates of pair spawning at elevated CO2 levels. Despite the higher risk of sperm competition found at elevated CO2, we also found a trend of lower satellite and sneaker male paternity at elevated CO2 Given the importance of fish for food security and ecosystem stability, this study highlights the need for targeted research into the effects of rising CO2 levels on patterns of reproduction in wild fish. Copyright © 2016 The Author(s).
Keywords: *Carbon Dioxide/ch [Chemistry]; *Perciformes/ph [Physiology]; *Reproduction/ph [Physiology]; *Seawater/ch [Chemistry]; *Sexual Behavior, Animal; Alternative reproductive tactics; Animals; CO2 vent; Carbon Dioxide; Climate change; Hydrogen-Ion Concentration; Labrid; Labridae; Male; Oceans and Seas; Perciformes; Reproduction; Seawater; Sexual Behavior, Animal; Symphodus ocellatus; acidification; animal; anthropogenic effect; carbon dioxide; carbon emission; chemistry; climate change; concentration (composition); courtship; dept.psy; ecological stability; food security; male; pH; paternity; perciform; physiology; reproduction; reproductive behavior; sea; sea water; sexual behavior; spawning population; sperm competition; wild population

Human choices between variable and fixed rewards in hypothetical variable‐delay and double‐reward discounting procedures - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2016)
Prior research has shown that nonhumans show an extreme preference for variable-over fixed-delays to reinforcement. This well-established preference for variability occurs because a reinforcer's strength or “value” decreases according to a curvilinear function as its delay increases. The purpose of the present experiments was to investigate whether this preference for variability occurs with human participants making hypothetical choices. In three experiments, participants recruited from Amazon Mechanical Turk made choices between variable and fixed monetary rewards. In a variable-delay procedure, participants repeatedly chose between a reward delivered either immediately or after a delay (with equal probability) and a reward after a fixed delay (Experiments 1 and 2). In a double-reward procedure, participants made choices between an alternative consisting of two rewards, one delivered immediately and one after a delay, and a second alternative consisting of a single reward delivered after a delay (Experiments 1 and 3). Finally, all participants completed a standard delay-discounting task. Although we observed both curvilinear discounting and magnitude effects in the standard discounting task, we found no consistent evidence of a preference for variability-as predicted by two prominent models of curvilinear discounting (i.e., a simple hyperbola and a hyperboloid)-in our variable-delay and double-reward procedures. This failure to observe a preference for variability may be attributed to the hypothetical, rule-governed nature of choices in the present study. In such contexts, participants may adopt relatively simple strategies for making more complex choices.
Keywords: dept.psy; peer-reviewed

A longitudinal follow-up study of happiness and meaning-making - Abe, Jo Ann A. (The Journal of Positive Psychology, 2016)
The long-term outcomes associated with happiness and meaning-making were examined by following up on participants in previous studies on experiential learning an average of 2.5 years later. Measures of happiness and meaning-making were extracted by analyzing the participants' journals using a computerized text-analysis program. Happiness as assessed by a composite measure of positive emotionality showed weak associations with the measures of adaptive functioning, and was negatively correlated with optimism, as well as positively correlated with emotion suppression. By contrast, meaning-making as assessed by composite measures of cognitive processing and self-distancing was robustly positively correlated with almost all measures of adaptive functioning. Regression analyses revealed that the two measures of meaning and their interaction term accounted for 20-24% of the variance in predicting the outcome measures. This study revealed that there may be at times a trade-off between happiness and meaning-making as well as a reversal in their patterns of long-term outcomes.
Keywords: LIWC; dept.psy; follow up; happiness; longitudinal; meaning-making; regression analysis; self-distancing; text-analysis

Ovarian fluid allows directional cryptic female choice despite external fertilization. - Alonzo, Suzanne H; Stiver, Kelly A; Marsh-Rollo, Susan E (Nature Communications, 2016)
In species with internal fertilization, females can favour certain males over others, not only before mating but also within the female's reproductive tract after mating. Here, we ask whether such directional post-mating (that is, cryptic) female mate choice can also occur in species with external fertilization. Using an in vitro sperm competition experiment, we demonstrate that female ovarian fluid (ovarian fluid) changes the outcome of sperm competition by decreasing the importance of sperm number thereby increasing the relative importance of sperm velocity. We further show that ovarian fluid does not differentially affect sperm from alternative male phenotypes, but generally enhances sperm velocity, motility, straightness and chemoattraction. Under natural conditions, female ovarian fluid likely increases the paternity of the preferred parental male phenotype, as these males release fewer but faster sperm. These results imply females have greater control over fertilization and potential to exert selection on males in species with external fertilization than previously thought possible.
Keywords: *Body Fluids/me [Metabolism]; *Choice Behavior/ph [Physiology]; *Fertilization/ph [Physiology]; *Ovary/me [Metabolism]; *Spermatozoa/ph [Physiology]; Animals; Body Fluids; Choice Behavior; Female; Fertilization; Male; Ovary; Perciformes; Perciformes/ph [Physiology]; Reproduction; Reproduction/ph [Physiology]; Sexual Behavior, Animal; Sexual Behavior, Animal/ph [Physiology]; Sperm Count; Spermatozoa; animal; body fluid; decision making; dept.psy; experimental study; female; fertilization; fertilization (reproduction); in vitro study; liquid; male; mate choice; metabolism; ovary; paternity; phenotype; physiology; reproduction; sexual behavior; species; sperm; sperm competition; spermatozoon; spermatozoon count; spermatozoon motility; thinking

Age-related effects of chronic restraint stress on ethanol drinking, ethanol-induced sedation, and on basal and stress-induced anxiety response. - Fernandez, Macarena Soledad; Fabio, Maria Carolina; Miranda-Morales, Roberto Sebastian; Virgolini, Miriam B; De Giovanni, Laura N; Hansen, Cristian; Wille-Bille, Aranza; Nizhnikov, Michael E; Spear, Linda P; Pautassi, Ricardo Marcos (Alcohol, 2016)
Adolescents are sensitive to the anxiolytic effect of ethanol, and evidence suggests that they may be more sensitive to stress than adults. Relatively little is known, however, about age-related differences in stress modulation of ethanol drinking or stress modulation of ethanol-induced sedation and hypnosis. We observed that chronic restraint stress transiently exacerbated free-choice ethanol drinking in adolescent, but not in adult, rats. Restraint stress altered exploration patterns of a light-dark box apparatus in adolescents and adults. Stressed animals spent significantly more time in the white area of the maze and made significantly more transfers between compartments than their non-stressed peers. Behavioral response to acute stress, on the other hand, was modulated by prior restraint stress only in adults. Adolescents, unlike adults, exhibited ethanol-induced motor stimulation in an open field. Stress increased the duration of loss of the righting reflex after a high ethanol dose, yet this effect was similar at both ages. Ethanol-induced sleep time was much higher in adult than in adolescent rats, yet stress diminished ethanol-induced sleep time only in adults. The study indicates age-related differences that may increase the risk for initiation and escalation in alcohol drinking. Copyright © 2016 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Anxiety/px [Psychology]; *Ethanol/ad [Administration & Dosage]; *Hypnotics and Sedatives/ad [Administration & Dosage]; *Stress, Psychological/px [Psychology]; Adolescent; Adult; Age Factors; Alcohol Drinking; Alcohol Drinking/ae [Adverse Effects]; Alcohol Drinking/bl [Blood]; Animals; Anxiety; Anxiety/bl [Blood]; Anxiety/et [Etiology]; Article; Chronic Disease; Ethanol; Ethanol/to [Toxicity]; Hypnotics and Sedatives; Hypnotics and Sedatives/to [Toxicity]; Male; Rat; Rats; Rats, Sprague-Dawley; Rats, Wistar; Restraint stress; Sprague Dawley rat; Stress, Psychological; Stress, Psychological/bl [Blood]; Stress, Psychological/co [Complications]; Wistar rat; acute stress; adverse effects; age; age distribution; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; anxiety; blood; body weight; chronic disease; complication; controlled study; corticosterone; corticosterone blood level; dept.psy; drinking behavior; etiology; hypnosis; hypnotic sedative agent; locomotion; male; mental stress; motor activity; mouse; nonhuman; open field test; peer-reviewed; psychology; rat; restrain stress; righting reflex; sedation; sex difference; sleep time; stimulus response; stress

The role of genes involved in stress, neural plasticity, and brain circuitry in depressive phenotypes: Convergent findings in a mouse model of neglect. - Montalvo-Ortiz, Janitza L; Bordner, Kelly A; Carlyle, Becky C; Gelernter, Joel; Simen, Arthur A; Kaufman, Joan (Behavioural brain research, 2016)
Early life neglect increases risk for the development of psychopathologies during childhood and adulthood, including depression and anxiety disorders. We recently reported epigenetic changes in DNA derived from saliva in three genes predicted depression in a cohort of maltreated children: DNA-binding protein inhibitor ID-3 (ID3), Glutamate NMDA Receptor (GRIN1), and Tubulin Polymerization Promoting Protein (TPPP). To validate the role of these genes in depression risk, secondary analyses were conducted of gene expression data obtained from medial prefrontal cortex (mPFC) tissue of mice subjected to a model of maternal neglect which included maternal separation and early weaning (MSEW). Anxiety and depression-like phenotype data derived using the elevated plus maze (EPM) and forced swimming test (FST), respectively, were also available for secondary analyses. Behavioral tests were conducted in MSEW and control adult male mice when they were between 65 and 80days old. ID3, GRIN1 and TPPP gene expression in the mPFC were found to significantly predict behavioral differences in the EPM and FST. These results further support the role of these genes in the etiology of depressive and anxiety phenotypes following early life stress. Copyright © 2016. Published by Elsevier B.V.
Keywords: *Depression/pa [Pathology]; *Gene Expression Regulation/ph [Physiology]; *Maternal Deprivation; *Neuronal Plasticity/ph [Physiology]; *Prefrontal Cortex/me [Metabolism]; *Stress, Psychological/pa [Pathology]; Animals; Article; C57BL mouse; DBA mouse; DNA-binding protein inhibitor ID-3 (ID3); Depression; Disease Models, Animal; GRIN1 gene; Gene Expression Regulation; Glutamate NMDA receptor (GRIN1); Gprin1 protein, mouse; ID3 gene; Idb3 protein, mouse; Inhibitor of Differentiation Proteins; Inhibitor of Differentiation Proteins/ge [Genetics]; Inhibitor of Differentiation Proteins/me [Metabolism]; Male; Maternal Deprivation; Maze Learning; Maze Learning/ph [Physiology]; Methylation; Mice; Mice, Inbred C57BL; Mice, Inbred DBA; Microarray Analysis; Neglect; Nerve Tissue Proteins; Nerve Tissue Proteins/ge [Genetics]; Nerve Tissue Proteins/me [Metabolism]; Neuronal Plasticity; Prefrontal Cortex; RNA, Messenger; RNA, Messenger/me [Metabolism]; Receptors, N-Methyl-D-Aspartate; Receptors, N-Methyl-D-Aspartate/ge [Genetics]; Receptors, N-Methyl-D-Aspartate/me [Metabolism]; Stress, Psychological; Swimming; Swimming/px [Psychology]; TPPP protein, mouse; Tubulin polymerization promoting protein (TPPP); animal; animal experiment; animal model; animal tissue; anxiety; connectome; controlled study; depression; dept.psy; disease activity; disease model; early life stress; gene; gene expression regulation; gene function; gene identification; gene location; genetics; inhibitor of differentiation protein; male; maternal deprivation; maze test; medial prefrontal cortex; mental stress; messenger RNA; metabolism; microarray analysis; molecular dynamics; molecular pathology; mouse; n methyl dextro aspartic acid receptor; nerve cell plasticity; nerve protein; nonhuman; pathology; peer-reviewed; phenotype; physiology; prediction; prefrontal cortex; priority journal; psychology; swimming; tubulin polymerization promoting protein gene

Transgenerational transmission of the effect of gestational ethanol exposure on ethanol Use‐Related behavior - Nizhnikov, Michael E; Popoola, Daniel O; Cameron, Nicole M (Alcoholism: Clinical and Experimental Research, 2016)
Background: Prenatal alcohol exposure (PAE) enhances the risk for alcoholism by increasing the propensity to consume alcohol and altering neurophysiological response to alcohol challenge. Trans-generationally transmittable genetic alterations have been implicated in these behavioral changes. To date, transgenerational transmission of PAE-induced behavioral responses to alcohol has never been experimentally investigated. Therefore, we explored the transgenerational transmission of PAE-induced behavioral effects across 3 generations. Methods: Pregnant Sprague Dawley dams received 1 g/kg ethanol (EtOH) or water daily on gestational days 17 through 20 via gavage, or remained untreated in their home cages. To produce second filial (F2) or F3 generations, similarly treated adult F1 or F2 offspring were mated and left undisturbed through gestation. On postnatal day (PND) 14, male and female F1, F2, and F3 offspring were tested for consumption of 5% (w/v) EtOH (in water), or water. Using the loss of righting reflex (LORR) paradigm on PND 42, F1 and F2 adolescent male offspring were tested for sensitivity to acute EtOH-induced sedation-hypnosis at 3.5 or 4.5 g/kg dose. F3 male adolescents were similarly tested at 3.5 g/kg dose. Blood EtOH concentration (BEC) was measured at waking. Results: EtOH exposure increased EtOH consumption compared to both water and untreated control groups in all generations. EtOH-treated group F1 and F2 adolescents displayed attenuated LORR duration compared to the water group. No attenuated LORR was observed in the F3 generation. BEC at waking corroborated with the significant LORR duration differences while also revealing differences between untreated control and water groups in F1 and F2 generations. Conclusions: Our results provide novel behavioral evidence attesting that late gestational moderate EtOH exposure increases EtOH intake across 3 generations and may alter sensitivity to EtOH-induced sedation-hypnosis across 2 generations. © 2016 Research Society on Alcoholism.
Keywords: Alcohol Drinking; Animals; Animals, Newborn; Article; Ethanol; Female; Infant; Intake; Loss of Righting Reflex; Male; Pregnancy; Prenatal Exposure Delayed Effects; Rat; Rats; Rats, Sprague-Dawley; Sprague Dawley rat; adult; alcohol; alcoholism; animal; animal experiment; behavior; behavior change; chemically induced; dept.psy; drinking behavior; epigenetics; female; genetics; hypnosis; male; newborn; nonhuman; pregnancy; prenatal exposure; priority journal; progeny; psychology; rat; righting reflex; sedation; transgenerational transmission; wakefulness; water

Very-Brief, Web-Based Interventions for Reducing Alcohol Use and Related Problems among College Students: A Review. - Leeman, Robert F; Perez, Elliottnell; Nogueira, Christine; DeMartini, Kelly S (Frontiers in psychiatry, 2015)
Very-brief, web-based alcohol interventions have great potential due to their convenience, ease of dissemination, and college students' stated preference for this intervention modality. To address the efficacy of these interventions, we conducted a review of the literature to identify randomized controlled trials (RCTs). Fifteen published reports were included. All RCTs meeting criteria for inclusion tested an intervention that featured personalized feedback on students' patterns of alcohol consumption. This review found some evidence to support the efficacy of very-brief, web-based interventions among college students for alcohol use reduction. Several trials, however, reported no evidence of efficacy and the methods of multiple trials raised concerns about potential bias that may have influenced study results. By contrast, this review did not yield evidence to support the efficacy of very-brief, web-based interventions for reduction of alcohol--related problems among college students. We found evidence to support the efficacy of two main types of intervention content: (a) focused solely on personalized normative feedback designed to correct misconceptions about peer alcohol consumption and (b) multi-component interventions. Future research is needed to test enhancements to very-brief, web-based interventions that feature personalized feedback on patterns of alcohol use and to determine for which types of college drinkers (e.g., heavier or lighter drinkers) these interventions are most efficacious. In addition, future studies are needed to test novel, very-brief, web-based interventions featuring approaches other than personalized feedback. In summary, this review yielded some evidence supporting very-brief, web-based interventions in reducing alcohol use but not related problems in college students. Very-brief, web-based interventions are worth pursuing given their convenience, privacy, and potential public health benefit.
Keywords: Computer; Effectiveness; Intervention; Motivational interviewing; Prevention; Review; Technology; Young adult; Youth; alcohol consumption; attitude to health; college student; dept.psy; evidence based practice; follow up; human; outcome assessment; peer group; peer-reviewed; personalized feedback; public health service; randomized controlled trial (topic); sample size; systematic error; very brief web based intervention

Age-related effects of restraint stress on ethanol intake and ethanol-induced narcosis - Pautassi, R. M.; Fernandez, M.; Nizhnikov, M.; Spear, L. P. (Alcohol and Alcoholism, 2015)
Keywords: dept.psy; ⛔ No DOI found

Should police use ACID? Training and credibility assessment using transcripts versus recordings - Colwell, Kevin; James-Kangal, Neslihan; Hiscock-Anisman, Cheryl; Phelan, Vivian (Journal of Forensic Psychology Practice, 2015)
There is a need for an applicable system of investigative interviewing and credibility assessment that extends science to practice. Experiment 1: Officers assessed the credibility of colleagues in a face-to-face interaction. Fourteen of sixteen officers were wrong in determining whether their colleague was responding honestly to them or lying to them. Experiment 2 compared untrained officers to officers trained in Assessment Criteria Indicative of Deception (ACID) in their ability to assess the credibility of statements regarding real and mock crimes by analyzing either verbatim transcripts or audio recordings. Officers who were trained in ACID performed significantly better after training than before, and significantly better than a group of officers who were never trained in ACID (89% correct versus 53% correct). No differences emerged due to analyzing transcripts versus recordings. The practical aspects of these results are discussed, including success rate, ease of application, and ease of training. The theoretical discussion includes differential recall enhancement and impression management. Finally, limitations and suggestions for future research are presented.
Keywords: Article; Assessment Criteria Indicative of Deception (ACID); adult; assessment criteria indicative of deception; audio recording; clinical assessment tool; controlled study; credibility assessment; criminal justice; deception; decision making; dept.psy; diagnostic accuracy; differential recall enhancement; human; human experiment; investigative interviewing; police; recall; scoring system; task performance; training; verbal behavior; videorecording; visual stimulation; word recognition; written language

Prenatal ethanol increases ethanol intake throughout adolescence, alters ethanol-mediated aversive learning, and affects μ but not δ or κ opioid receptor mRNA expression - Fabio, María Carolina; Macchione, Ana Fabiola; Nizhnikov, Michael E.; Pautassi, Ricardo Marcos (European Journal of Neuroscience, 2015)
Animal models of prenatal ethanol exposure (PEE) have indicated a facilitatory effect of PEE on adolescent ethanol intake, but few studies have assessed the effects of moderate PEE throughout adolescence. The mechanisms underlying this facilitatory effect remain largely unknown. In the present study, we analysed ethanol intake in male and female Wistar rats with or without PEE (2.0 g/kg, gestational days 17-20) from postnatal days 37 to 62. The results revealed greater ethanol consumption in PEE rats than in controls, which persisted throughout adolescence. By the end of testing, ethanol ingestion in PEE rats was nearly 6.0 g/kg. PEE was associated with insensitivity to ethanol-induced aversion. PEE and control rats were further analysed for levels of μ, δ and κ opioid receptor mRNA in the infralimbic cortex, nucleus accumbens shell, and ventral tegmental area. Similar levels of mRNA were observed across most areas and opioid receptors, but μ receptor mRNA in the ventral tegmental area was significantly increased by PEE. Unlike previous studies that assessed the effects of PEE on ethanol intake close to birth, or in only a few sessions during adolescence, the present study observed a facilitatory effect of PEE that lasted throughout adolescence. PEE was associated with insensitivity to the aversive effect of ethanol, and increased levels of μ opioid receptor transcripts. PEE is a prominent vulnerability factor that probably favors the engagement of adolescents in risky trajectories of ethanol use. © 2015 Federation of European Neuroscience Societies and John Wiley & Sons Ltd.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Avoidance Learning/de [Drug Effects]; *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; *Receptors, Opioid, delta/me [Metabolism]; *Receptors, Opioid, kappa/me [Metabolism]; Adolescent; Age Factors; Alcohol Drinking; Animals; Article; Aversive conditioning; Avoidance Learning; Central Nervous System Depressants; Ethanol; Ethanol intake; Female; Male; Opioid receptors; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Prenatal ethanol; RNA isolation; RNA, Messenger; RNA, Messenger/me [Metabolism]; Rats; Rats, Wistar; Receptors, Opioid, delta; Receptors, Opioid, delta/ge [Genetics]; Receptors, Opioid, kappa; Receptors, Opioid, kappa/ge [Genetics]; Wistar rat; adolescence; adolescent; age; alcohol; alcohol consumption; alcohol intoxication; animal; animal experiment; animal model; aversion; aversive behavior; aversive conditioning; avoidance behavior; body weight; central depressant agent; chemically induced; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; ethanol intake; facilitation; female; fluid intake; genetics; glyceraldehyde 3 phosphate dehydrogenase; kappa opiate receptor; male; messenger RNA; metabolism; microdissection; motivation; mu opiate receptor; nonhuman; opioid receptors; pathophysiology; place preference; polymerase chain reaction; pregnancy; prenatal ethanol; prenatal ethanol exposure; prenatal exposure; priority journal; protein expression; quantitative analysis; rat; reinforcement; reverse transcription; sigma opiate receptor; sugar intake

Differential emotions theory as a theory of personality development - Abe, Jo Ann A. (Emotion Review, 2015)
In The Face of Emotions, which was Carroll Izard's first major attempt at elaborating his differential emotions theory (DET), he stated that the book presents a theoretical framework for the study of emotions and their role in personality and interpersonal processes. Yet, over the years, his contribution to personality theory has generally been overshadowed by the attention focused on his views on facial expressions and the structure of emotions. This article will begin with a brief overview of the DET perspective on personality development. Then, it will examine how the DET framework can be used to organize recent findings from three lines of research on adult personality. It will conclude with suggestions for future research as well as some personal recollections.
Keywords: dept.psy; differential emotions theory; emotions; personality development

Introduction: special section to honor carroll izard - Abe, Jo Ann A.; Schultz, David (Emotion Review, 2015)
Keywords: dept.psy

Endogenous opioids as substrates for ethanol intake in the neonatal rat: The impact of prenatal ethanol exposure on the opioid family in the early postnatal period. - Bordner, Kelly; Deak, Terrence (Physiology & Behavior, 2015)
BACKGROUND: Despite considerable knowledge that prenatal ethanol exposure can lead to devastating effects on the developing fetus, alcohol consumption by pregnant women remains strikingly prevalent. Both clinical and basic research has suggested that, in addition to possible physical, behavioral, and cognitive deficits, gestational exposure to alcohol may lead to an increased risk for the development of later alcohol-related use and abuse disorders. The current work sought to characterize alterations in endogenous opioid signaling peptides and gene expression produced by ethanol exposure during the last days of gestation., METHODS: Experimental subjects were 4-, 8-, and 12-day old infant rats obtained from pregnant females that were given daily intubations of 0, 1, or 2g/kg ethanol during the last few days of gestation (GDs 17-20). Using real-time RT-PCR, western blotting analysis, and enzyme immunoassays, we examined mRNA and protein for three opioid receptors and ligands in the nucleus accumbens, ventral tegmental area, and hypothalamus., RESULTS: Three main trends emerged - (1) mRNA for the majority of factors was found to upregulate across each of the three postnatal ages assessed, indicative of escalating ontogenetic expression of opioid-related genes; (2) prenatal ethanol significantly reduced many opioid peptides, suggesting a possible mechanism by which prenatal exposure can affect future responsiveness towards ethanol; and (3) the nucleus accumbens emerged as a key site for ethanol-dependent effects, suggesting a potential target for additional assessment and intervention towards understanding the ethanol's ability to program the developing brain., CONCLUSION: We provide a global assessment of relatively long-term changes in both opioid gene expression and protein following exposure to only moderate amounts of ethanol during a relatively short window in the prenatal period. These results suggest that, while continuing to undergo ontogenetic changes, the infant brain is sensitive to prenatal ethanol exposure and that such exposure may lead to relatively long-lasting changes in the endogenous opioid system within the reward circuitry. These data indicate a potential mechanism and target for additional assessments of ethanol's ability to program the brain, affecting later responsiveness towards the drug. Copyright © 2015 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/pp [Physiopathology]; *Central Nervous System Depressants/pd [Pharmacology]; *Ethanol/pd [Pharmacology]; *Gene Expression Regulation, Developmental/de [Drug Effects]; *Prenatal Exposure Delayed Effects/pp [Physiopathology]; *Receptors, Opioid/me [Metabolism]; Age Factors; Alcohol Drinking; Analysis of Variance; Animals; Animals, Newborn; Article; Brain; Brain/gd [Growth & Development]; Brain/me [Metabolism]; Central Nervous System Depressants; Dynorphins; Dynorphins/ge [Genetics]; Dynorphins/me [Metabolism]; Enkephalins; Enkephalins/ge [Genetics]; Enkephalins/me [Metabolism]; Ethanol; Female; Gene Expression Regulation, Developmental; Gestational Age; MRNA; Male; Ontogeny; Opioids; Pregnancy; Prenatal Exposure Delayed Effects; Pro-Opiomelanocortin; Pro-Opiomelanocortin/ge [Genetics]; Pro-Opiomelanocortin/me [Metabolism]; Protein; Protein Precursors; Protein Precursors/ge [Genetics]; Protein Precursors/me [Metabolism]; RNA, Messenger; RNA, Messenger/me [Metabolism]; Rat; Rats; Rats, Sprague-Dawley; Receptors, Opioid; Receptors, Opioid/ge [Genetics]; Sprague Dawley rat; Western blotting; age; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal tissue; beta endorphin; brain; brain development; central depressant agent; controlled study; delta opiate receptor; dept.psy; drinking behavior; drug effects; dynorphin; endorphin; enkephalin; enzyme immunoassay; female; gene expression; gene expression regulation; genetics; gestation period; gestational age; growth, development and aging; hypothalamus; infant; kappa opiate receptor; male; messenger RNA; metabolism; mu opiate receptor; newborn; nonhuman; nucleus accumbens; ontogeny; opiate receptor; pathophysiology; peer-reviewed; perinatal period; postnatal development; pre-prodynorphin; pregnancy; prenatal exposure; preprodynorphin; preproenkephalin; priority journal; proopiomelanocortin; protein; protein precursor

Change in the hedonic value of an aversive stimulus in the presence of a pre-exposed odor. - Kamenetzky, Giselle V; Suarez, Andrea B; Pautassi, Ricardo M; Mustaca, Alba E; Nizhnikov, Michael E (Physiology & behavior, 2015)
Rats exhibit a sensitive period from the time of birth until postnatal day 10 during which they develop preferences for odors even if those odors are paired with a moderately aversive stimulus. It is still unknown whether pre-exposure to an odor produces alterations on intake responses of basic tastants, and on other patterns that indicate a change in the hedonic value of reward, such as nipple grasping behavior. The current study assessed the effect of pre-exposure to an odor immediately after birth on intake responses of appetitive and aversive tastants. The objectives were to assess if 3-hour-old rats adjust their behaviors to obtain different values of appetitive and aversive rewards in the presence of a familiar odor. Specifically we wanted to determine whether the intake of saccharin or quinine, administered through the artificial nipple, increases in the presence of the familiar odor. Results showed that 3-hour-old rats differentially respond to two different concentrations of saccharin and two concentrations of quinine. In the presence of the pre-exposed odor newborn rats increased intake and grasp responses to the artificial nipple containing quinine. This effect disappeared with a higher concentration of quinine. These results suggest that the pre-exposed odor generated a change in the hedonic value of the aversive reward. Copyright © 2014 Elsevier Inc. All rights reserved.
Keywords: *Avoidance Learning/ph [Physiology]; *Conditioning, Psychological/ph [Physiology]; *Discrimination, Psychological/ph [Physiology]; *Emotions/ph [Physiology]; *Odorants; *Smell/ph [Physiology]; Age Factors; Analgesics, Non-Narcotic; Animals; Animals, Newborn; Appetitive Behavior; Appetitive Behavior/ph [Physiology]; Article; Aversive solutions; Avoidance Learning; Conditioning (Psychology); Discrimination (Psychology); Dose-Response Relationship, Drug; Emotions; Female; Male; Newborn rats; Odors; Olfactory learning; Ontogeny; Quinine; Quinine/ad [Administration & Dosage]; Rats; Rats, Sprague-Dawley; Reaction Time; Reaction Time/de [Drug Effects]; Reaction Time/ph [Physiology]; Saccharin; Saccharin/ad [Administration & Dosage]; Smell; Sprague Dawley rat; Sweetening Agents; age; analgesic agent; animal; animal behavior; animal experiment; appetite; aversion; avoidance behavior; birth; bitter taste; conditioning; controlled study; dept.psy; dose response; drug effects; emotion; exposure; female; food intake; grip strength; gustatory system; male; newborn; nipple; nonhuman; odor; peer-reviewed; perceptive discrimination; physiology; priority journal; quinine; rat; reaction time; reward; saccharin; stimulus; sweetening agent; taste

Can low-level ethanol exposure during pregnancy influence maternal care? An investigation using two strains of rat across two generations. - Popoola, Daniel O; Borrow, Amanda P; Sanders, Julia E; Nizhnikov, Michael E; Cameron, Nicole M (Physiology & behavior, 2015)
Gestational alcohol use is well documented as detrimental to both maternal and fetal health, producing an increase in offspring's tendency for alcoholism, as well as in behavioral and neuropsychological disorders. In both rodents and in humans, parental care can influence the development of offspring physiology and behavior. Animal studies that have investigated gestational alcohol use on parental care and/or their interaction mostly employ heavy alcohol use and single strains. This study aimed at investigating the effects of low gestational ethanol dose on parental behavior and its transgenerational transmission, with comparison between two rat strains. Pregnant Sprague Dawley (SD) and Long Evans (LE) progenitor dams (F0) received 1g/kg ethanol or water through gestational days 17-20 via gavage, or remained untreated in their home cages. At maturity, F1 female offspring were mated with males of the same strain and treatment and were left undisturbed through gestation. Maternal behavior was scored in both generations during the first six postnatal days. Arch-back nursing (ABN) was categorized as: 1, when the dam demonstrated minimal kyphosis; 2, when the dam demonstrated moderate kyphosis; and 3, when the dam displayed maximal kyphosis. Overall, SD showed greater amounts of ABN than LE dams and spent more time in contact with their pups. In the F0 generation, water and ethanol gavage increased ABN1 and contact with pups in SD, behaviors which decreased in treated LE. For ABN2, ethanol-treated SD dams showed more ABN2 than water-treated dams, with no effect of treatment on LE animals. In the F1 generation, prenatal exposure affected retrieval. Transgenerational transmission of LG was observed only in the untreated LE group. Strain-specific differences in maternal behavior were also observed. This study provides evidence that gestational gavage can influence maternal behavior in a strain-specific manner. Our results also suggest that the experimental procedure during gestation and genetic variations between strains may play an important role in the behavioral effects of prenatal manipulations. Copyright © 2015 Elsevier Inc. All rights reserved.
Keywords: *Central Nervous System Depressants/to [Toxicity]; *Ethanol/to [Toxicity]; *Maternal Behavior; *Prenatal Exposure Delayed Effects/ci [Chemically Induced]; Alcohol Drinking; Alcohol Drinking/pp [Physiopathology]; Analysis of Variance; Animals; Animals, Newborn; Article; Central Nervous System Depressants; Ethanol; Female; Grooming; Intragastric gavage; Long Evans rat; Male; Maternal Behavior; Maternal care; Posture; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal Exposure Delayed Effects/nu [Nursing]; Prenatal Exposure Delayed Effects/pp [Physiopathology]; Rat; Rats; Rats, Long-Evans; Rats, Sprague-Dawley; Species Specificity; Sprague Dawley rat; Time Factors; Transgenerational; alcohol; alcohol consumption; analysis of variance; animal; animal experiment; animal model; body posture; central depressant agent; chemically induced; controlled study; dept.psy; drinking behavior; female; genetic variability; grooming; kyphosis; licking; male; maternal behavior; maternal care; mating; newborn; nonhuman; nursing; parental behavior; pathophysiology; peer-reviewed; pregnancy; prenatal exposure; priority journal; progeny; rat; species difference; time

Neural gene expression profiles and androgen levels underlie alternative reproductive tactics in the ocellated wrasse, symphodus ocellatus - Stiver, Kelly A.; Harris, Rayna M.; Townsend, Jeffrey P.; Hofmann, Hans A.; Alonzo, Suzanne H. (Ethology, 2014)
Discrete variation in reproductive behavior and physiology is observed in diverse taxa. Although it is known that most within-sex alternative reproductive tactics arise as a consequence of phenotypic plasticity, relatively little is known about differential neural gene expression among plastic alternative reproductive phenotypes. In the ocellated wrasse Symphodus ocellatus, males exhibit one of three alternative tactics (nesting, satellite, and sneaker) within a reproductive season, but switch tactics between years. Satellites and sneakers spawn parasitically in dominant (nesting) males' nests, but only nesting males provide parental care. Nesting and satellite males show transient cooperative defense of nests against sneakers. Here, we analyze circulating sex steroid hormone levels and neural gene expression profiles in these three male phenotypes and in females. 11-ketotestosterone (but not testosterone) was highest in nesting males, while estradiol was highest in females. Brain transcriptomes of satellites and females were most similar to each other and intermediate to nesting and sneaker males. Sneakers showed more total expression differences, whereas nesting males showed higher magnitude expression differences. Our findings reveal the surprising extent to which neural gene expression patterns vary across reproductive tactics that vary in a number of social traits, including aggression, territoriality, and cooperation, providing important insights into the molecular mechanisms that may underlie variation in cooperative and reproductive behavior. © 2014 Blackwell Verlag GmbH.
Keywords: Androgens; Competition; Cooperation; Mating tactic; Microarray; Reproduction; Symphodus ocellatus; dept.psy

Rats' choices with token stimuli in concurrent variable- interval schedules - Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2014)
Four rats responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights arranged vertically above each of two side levers). During exchange periods, each token could be exchanged for one food pellet by responding on a center lever, with one response required for each pellet delivery. In different conditions, the exchange requirements (number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response levers. The experiments were closely patterned after research with pigeons by Mazur and Biondi (), and the results from the rats in the present experiment were similar. Response percentages on the two levers changed as each additional token was earned, and these patterns indicated that choice was controlled by both the time to the exchange periods and the number of food pellets that were delivered in the exchange period. In some conditions, the exchange requirement was three tokens for each lever, but the token lights were not turned on as they were earned for one of the two keys. The rats showed a slight preference for the lever without the token lights, which may indicate that the token lights were not serving as conditioned reinforcers (a result also found by Mazur and Biondi with pigeons). Overall, these results suggest that, in this choice procedure, the token stimuli served primarily as discriminative stimuli that signaled the temporal proximity and quantity of the primary reinforcer, food.
Keywords: Animals; Choice Behavior; Concurrent variable-interval schedules; Conditioned reinforcers; Conditioning, Operant; Cues; Discriminative stimuli; Hyperbolic discounting; Lever press; Long Evans rat; Male; Rats; Rats, Long-Evans; Reinforcement Schedule; Token Economy; Token stimuli; animal; association; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; rat; reinforcement

Hope, will, purpose, competence, and fidelity: ego strengths as predictors of career identity - Anthis, Kristine (Identity, 2014)
This correlational study examined the relationships among ego strengths and career identity. Self-report data were collected from a sample of university undergraduates (N = 239). Participants completed the Psychosocial Inventory of Ego Strengths and the Vocational Identity Status Assessment. The results revealed gender differences, primarily in career identity. The findings also showed that the unique variance explained in career identity by each ego strength was modest, indicating that the best predictor of career identity is the overall level of ego strengths. Suggestions for future research, such as longitudinal designs to establish ego strengths as developmental precursors of career identity, are provided. © 2014 Copyright Taylor & Francis Group, LLC.
Keywords: dept.psy

Adaptation and Sexual Offending - Camilleri, Joseph A.; Stiver, Kelly A. (Evolutionary Perspectives on Human Sexual Psychology and Behavior, 2014)
Agreement on the causes of sexual offending has eluded scholars because of an emphasis on studying proximate causes—as with crime in general, there are numerous variables that correlate with sexual offending. A more consilient view of sexual offending includes an evolutionary approach that attempts to answer ultimately why such behavior exists. To guide this research, Camilleri (The Oxford handbook of evolutionary perspectives on violence, homicide, and war, New York, 173–196) proposed a typology of sexual offenders that classifies offending based on two dimensions: (1) whether the behavior is an adaptation, by-product, or disorder and (2) if the mechanism is obligate or facultative. Categories resulting from this typology seem to capture the variability of sexual offending behavior. This chapter mostly reviews evidence of how sexual offending could function as an adaptation, draws links from nonhuman behavior literature, and briefly reviews alternative explanations, including by-products and disorders.
Keywords: Antisocial Behavior; Nonhuman Animal; Psychopathic Trait; Sexual Coercion; Sexual Offender; dept.psy

Brief prenatal ethanol exposure alters behavioral sensitivity to the kappa opioid receptor agonist (U62,066E) and antagonist (Nor‐BNI) and reduces kappa opioid receptor expression - Nizhnikov, Michael E; Pautassi, Ricardo Marcos; Carter, Jenna M; Landin, Justine D; Varlinskaya, Elena I; Bordner, Kelly A; Werner, David F; Spear, Norman E (Alcoholism: Clinical and Experimental Research, 2014)
Background: Approximately 10 to 15% of women consume alcohol (ethanol [EtOH]) during pregnancy in the United States. Even low amounts of EtOH consumption during pregnancy can elicit long-term consequences. Prenatal experience with as few as 3 drinks has been associated with increase problem drinking in adulthood. Such effects are corroborated in rodents; however, the underlying neural adaptations contributing to this effect are not clear. In the current set of experiments, we investigated whether changes in EtOH responding following prenatal EtOH exposure involved kappa opioid receptor activation and expression. Methods: Sprague-Dawley rats were prenatally exposed to low levels of alcohol (1.0 g/kg) during late gestation (gestational days 17 to 20 [GD17-20]) via intragastric intubation of pregnant dams. Following birth, EtOH intake, kappa- and mu-opioid-induced place conditioning, and kappa opioid receptor expression in mesolimbic brain regions were assessed in infant rats (postnatal days 14 to 15 [PD14-15]) that were offspring of dams given EtOH, vehicle, or untreated, during pregnancy. Results: Animals exposed to prenatal alcohol drank more alcohol later in life and exhibited significant changes in the kappa opioid system. While control subjects found kappa opioid activation aversive, animals exposed to EtOH prenatally exhibited either no aversion or appetitive responding. Further analysis revealed that synaptosomal kappa opioid receptor expression was significantly decreased in brain areas implicated in responding to EtOH. Conclusions: Overall, these data suggest that prenatal EtOH affects kappa opioid function and expression and that these changes may be involved in increased drinking later in life. © 2014 by the Research Society on Alcoholism.
Keywords: Alcohol Drinking; Animals; Brain Chemistry; Conditioning (Psychology); Ethanol; Female; Gene Expression; Infant; Kappa; Male; Naltrexone; Opioid; Pregnancy; Prenatal Exposure Delayed Effects; Pyrrolidines; Rats; Rats, Sprague-Dawley; Receptors, Opioid, kappa; Sprague Dawley rat; Western blotting; agonists; alcohol; alcohol abuse; alcohol consumption; analogs and derivatives; animal; animal experiment; animal tissue; antagonists and inhibitors; article; behavioral science; biosynthesis; brain level; chemically induced; conditioning; controlled study; dept.psy; drinking behavior; drug effects; drug therapy; female; fluid intake; gene expression; gestation period; kappa opiate receptor; kappa opiate receptor antagonist; limbic cortex; male; metabolism; naltrexone; nonhuman; nor bni; norbinaltorphimine; pregnancy; prenatal exposure; priority journal; protein expression; pyrrolidine derivative; rat; spiradoline; spiradoline mesilate; unclassified drug

Development of phonological constancy: 19-Month-Olds, but not 15-Month-Olds, identify words in a non-native regional accent - Mulak, Karen E.; Best, Catherine T.; Tyler, Michael D.; Kitamura, Christine; Irwin, Julia R. (Child Development, 2013)
By 12months, children grasp that a phonetic change to a word can change its identity (phonological distinctiveness). However, they must also grasp that some phonetic changes do not (phonological constancy). To test development of phonological constancy, sixteen 15-month-olds and sixteen 19-month-olds completed an eye-tracking task that tracked their gaze to named versus unnamed images for familiar words spoken in their native (Australian) and an unfamiliar non-native (Jamaican) regional accent of English. Both groups looked longer at named than unnamed images for Australian pronunciations, but only 19-month-olds did so for Jamaican pronunciations, indicating that phonological constancy emerges by 19months. Vocabulary size predicted 15-month-olds' identifications for the Jamaican pronunciations, suggesting vocabulary growth is a viable predictor for phonological constancy development.
Keywords: Acoustic Stimulation; Female; Fixation, Ocular; Humans; Infant; Language Development; Male; Perceptual Masking; Phonetics; Psychomotor Performance; Recognition (Psychology); Speech Perception; Vocabulary; article; auditory stimulation; dept.psy; eye fixation; female; human; infant; language development; linguistics; male; perception; phonetics; physiology; psychomotor performance; recognition; speech perception

Pigeons' choices with token stimuli in concurrent variable-interval schedules: concurrent vi schedules with tokens - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2013)
Twelve pigeons responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights for some pigeons, and white circles on the response keys for others). During exchange periods, each token could be exchanged for food on a fixed-ratio 1 schedule. Across conditions, the exchange requirements ( number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response keys. The main findings were that the pigeons' response percentages varied as a function of the number of tokens earned at any given moment, and they were determined by both the delays to food and by the number of food deliveries in the exchange periods. In some conditions, tokens had to be earned but were not visible during the variable-interval schedules for one or both keys. When one key had visible tokens and the other did not, the pigeons showed a preference for the key without visible tokens. A model based on the matching law and a hyperbolic delay-discounting equation could account for the main patterns of choice responding, and for how response percentages changed as successive tokens were earned. The results are consistent with the view that the token stimuli served as discriminative stimuli that signaled the current delays to food.
Keywords: *Choice Behavior; *Token Economy; Animals; Columbidae; Concurrent variable-interval schedules; Conditioning, Operant; Generalized matching law; Hyperbolic discounting; Keypeck; Male; Models, Psychological; Pigeons; Reinforcement Schedule; Token stimuli; dept.psy; peer-reviewed

Assessment Criteria Indicative of Deception: An Example of the New Paradigm of Differential Recall Enhancement - Colwell, Kevin; Hiscock-Anisman, Cheryl; Fede, Jacquelyn (Applied Issues in Investigative Interviewing, Eyewitness Memory, and Credibility Assessment, 2013)
The present chapter details the historical and conceptual evolution of a new paradigm in statement analysis that has developed over the past 20 years. There has been an increasing awareness of the importance of interviewing designed to facilitate the detection of deception as a necessary component of statement analysis (Colwell, Hiscock, & Memon, 2002; Hartwig & Bond, 2011; Hernández-Fernaud & Alonso-Quecuty, 1997; Koehnken, Schimossek, Ascherman, & Hofer, 1995; Vrij, Fisher, Mann, & Leal, 2006). Subsequently, the work of multiple researchers has created a zeitgeist that has nurtured and informed the development of this new paradigm. This chapter begins by providing a quick overview of the various lines of research that comprise this paradigm. Attention is then given to credibility assessment and statement content criteria that discriminate honest from deceptive responding. Then, the focus is on strategies of impression management and the subjective experience of respondents during an investigative interview. This sets the stage for a discussion of investigative interviewing structure and techniques that facilitate the detection of deception through the process of differential recall enhancement (DRE: Colwell et al., 2012). Finally, this chapter considers in detail an approach to interviewing and assessment that is representative of the new paradigm.
Keywords: Content Criterion; Free Recall; Impression Management; Present Volume; Target Event; dept.psy

Sharing of potential nest sites by Etheostoma olmstedi males suggests mutual tolerance in an alloparental species. - Stiver, Kelly A; Wolff, Stephen H; Alonzo, Suzanne H (PloS one, 2013)
When reproductive competitors tolerate or cooperate with one another, they may gain particular benefits, such as collectively guarding resources or attracting mates. Shared resources may be those essential to reproduction, such as a breeding site or nest. Using the tessellated darter, a species where males but not females compete over potential nest sites, we examined site use and sharing under controlled conditions of differing competitor density. Sharing was observed even when competitor density was low and individuals could have each occupied a potential nest site without same-sex sharing. Males were more likely to share a nest site with one other when the difference in size between them was larger rather than smaller. There was no evidence that female sharing was dependent on their relative size. Fish were generally more likely to use and share larger sites, in accordance with the greater relative surface area they offered. We discuss how one or both sharing males may potentially benefit, and how male sharing of potential nest sites could relate to female mating preferences. Tessellated darter males are known to provide alloparental care for eggs but this occurs without any social contact between the alloparent and the genetic father of the young. Thus, the suggestion that they may also share sites and maintain social contact with reproductive competitors highlights the importance of increased focus on the potential complexity of reproductive systems.
Keywords: *Behavior, Animal; *Nesting Behavior; *Perches/ph [Physiology]; *Reproduction; Animals; Behavior, Animal; Etheostoma olmstedi; Female; Male; Nesting Behavior; Perches; Reproduction; Sexual Behavior, Animal; animal behavior; article; competitor species; controlled study; dept.psy; female; fish; male; male animal; mate choice; nesting; nonhuman; peer-reviewed; population density; population size; sex difference; social behavior; symbiosis

Maternal separation with early weaning: A rodent model providing novel insights into neglect associated developmental deficits - Carlyle, Becky C.; Duque, Alvaro; Kitchen, Robert R.; Bordner, Kelly A.; Coman, Daniel; Doolittle, Eliza; Papademetris, Xenophonios; Hyder, Fahmeed; Taylor, Jane R.; Simen, Arthur A. (Development and Psychopathology, 2012)
Child neglect is the most prevalent form of child maltreatment in the United States, and poses a serious public health concern. Children who survive such episodes go on to experience long-lasting psychological and behavioral problems, including higher rates of post-traumatic stress disorder symptoms, depression, alcohol and drug abuse, attention-deficit/hyperactivity disorder, and cognitive deficits. To date, most research into the causes of these life-long problems has focused on well-established targets such as stress responsive systems, including the hypothalamus-pituitary-adrenal axis. Using the maternal separation and early weaning model, we have attempted to provide comprehensive molecular profiling of a model of early-life neglect in an organism amenable to genomic manipulation: the mouse. In this article, we report new findings generated with this model using chromatin immunoprecipitation sequencing, diffuse tensor magnetic resonance imaging, and behavioral analyses. We also review the validity of the maternal separation and early weaning model, which reflects behavioral deficits observed in neglected humans including hyperactivity, anxiety, and attentional deficits. Finally, we summarize the molecular characterization of these animals, including RNA profiling and label-free proteomics, which highlight protein translation and myelination as novel pathways of interest.
Keywords: Animals; Anxiety; Attention; Behavior, Animal; Brain; C57BL mouse; Child; Child Abuse; Chromatin Immunoprecipitation; Developmental Disabilities; Diffusion Tensor Imaging; Disease Models, Animal; Epigenesis, Genetic; Humans; Maternal Deprivation; Mice; Mice, Inbred C57BL; Prefrontal Cortex; Proteomics; RNA; Weaning; animal; animal behavior; anxiety; article; attention; brain; child; child abuse; chromatin immunoprecipitation; dept.psy; developmental disorder; diffusion tensor imaging; disease model; genetic epigenesis; genetics; human; maternal deprivation; metabolism; mouse; pathophysiology; peer-reviewed; prefrontal cortex; proteomics; psychological aspect; weaning

Choice behavior of pigeons (Columba livia), college students, and preschool children (Homo sapiens) in the Monty Hall dilemma. - Mazur, James E; Kahlbaugh, Patricia E (Journal of Comparative Psychology, 2012)
In the Monty Hall dilemma, an individual chooses between three options, only one of which will deliver a prize. After the initial choice, one of the nonchosen options is revealed as a losing option, and the individual can choose to stay with the original choice or switch to the other remaining option. Previous studies have found that most adults stay with their initial choice, although the chances of winning are 2/3 for switching and 1/3 for staying. Pigeons, college students, and preschool children were given many trials on this task to examine how their choices might change with experience. The college students began to switch on a majority of trials much sooner than the pigeons, contrary to the findings by Herbranson and Schroeder (2010) that pigeons perform better than people on this task. In all three groups, some individuals approximated the optimal strategy of switching on every trial, but most did not. Many of the preschoolers immediately showed a pattern of always switching or always staying and continued this pattern throughout the experiment. In a condition where the probability of winning was 90% after a switch, all college students and all but one pigeon learned to switch on nearly every trial. The results suggest that one main impediment to learning the optimal strategy in the Monty Hall task, even after repeated trials, is the difficulty in discriminating the different reinforcement probabilities for switching versus staying.
Keywords: *Choice Behavior; *Columbidae; Adolescent; Animals; Child, Preschool; Choice Behavior; College students; Columbidae; Female; Games, Experimental; Humans; Male; Monty hall dilemma; Pigeons; Preschool children; Probability; Reinforcement Schedule; Reinforcement probability; Reward; Students; Students/px [Psychology]; Young Adult; adolescent; adult; animal; article; decision making; dept.psy; female; game; human; male; pigeons and doves; preschool child; probability; psychological aspect; reinforcement; reward; student

What lexical decision and naming tell us about reading - Katz, Leonard; Brancazio, Larry; Irwin, Julia; Katz, Stephen; Magnuson, James; Whalen, D. H. (Reading and Writing, 2012)
The lexical decision (LD) and naming (NAM) tasks are ubiquitous paradigms that employ printed word identification. They are major tools for investigating how factors like morphology, semantic information, lexical neighborhood and others affect identification. Although use of the tasks is widespread, there has been little research into how performance in LD or NAM relates to reading ability, a deficiency that limits the translation of research with these tasks to the understanding of individual differences in reading. The present research was designed to provide a link from LD and NAM to the specific variables that characterize reading ability (e.g., decoding, sight word recognition, fluency, vocabulary, and comprehension) as well as to important reading-related abilities (phonological awareness and rapid naming). We studied 99 adults with a wide range of reading abilities. LD and NAM strongly predicted individual differences in word identification, less strongly predicted vocabulary size and did not predict comprehension. Fluency was predicted but with differences that depended on the way fluency was defined. Finally, although the tasks did not predict individual differences in rapid naming or phonological awareness, the failures nevertheless assisted in understanding the cognitive mechanisms behind these reading-related abilities. The results demonstrate that LD and NAM are important tools for the study of individual differences in reading.
Keywords: Lexical decision; Naming; RT; Reading ability; dept.hls; dept.psy; peer-reviewed

Cognitive-affective styles associated with position on war - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2012)
This study examined cognitive-affective styles associated with position on the Iraq war by analyzing responses posted on an online discussion forum using a computerized text-analysis program (Linguistic Inquiry and Word Count). Overall, the results were consistent with those obtained in narrative-coding studies. The pro-war group was associated with an external focus and a simplistic style of information processing. The anti-war group was associated with an internal focus and high levels of cognitive processing and negative emotion words. The “neither” group scored the highest on cognitive complexity and positive emotion words, and it was also the most balanced in terms of internal and external focus.
Keywords: Linguistic Inquiry and Word Count (LIWC); affective style; attitudes toward Iraq War; cognitive style; dept.psy; peer-reviewed

Eye movement dynamics and cognitive self-organization in typical and atypical development - Mirman, Daniel; Irwin, Julia R.; Stephen, Damian G. (Cognitive Neurodynamics, 2012)
This study analyzed distributions of Euclidean displacements in gaze (i.e. “gaze steps”) to evaluate the degree of componential cognitive constraints on audio-visual speech perception tasks. Children performing these tasks exhibited distributions of gaze steps that were closest to power-law or lognormal distributions, suggesting a multiplicatively interactive, flexible, self-organizing cognitive system rather than a component-dominant stipulated cognitive structure. Younger children and children diagnosed with an autism spectrum disorder (ASD) exhibited distributions that were closer to power-law than lognormal, indicating a reduced degree of self-organized structure. The relative goodness of lognormal fit was also a significant predictor of ASD, suggesting that this type of analysis may point towards a promising diagnostic tool. These results lend further support to an interaction-dominant framework that casts cognitive processing and development in terms of self-organization instead of fixed components and show that these analytical methods are sensitive to important developmental and neuropsychological differences.
Keywords: Autism; Development; Eye movements; Interaction-dominance; Self-organization; article; autism; cognition; dept.psy; eye movement; human; neuropsychology; speech perception

Teaching professionals to detect deception: the efficacy of a brief training workshop - Colwell, Lori H.; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hartwig, Maria; Cole, Lindsey D.; Werdin, Kathryn; Youschak, Kimberly E. (Journal of Forensic Psychology Practice, 2012)
Despite the importance of credibility assessments in forensic settings, research shows that forensic professionals are mediocre at this task. This study tested the efficacy of a 2.5-hour training workshop on Assessment Criteria Indicative of Deception (ACID), a system of investigative interviewing and credibility assessment using verbal content analysis, in a sample of 99 forensic professionals at a maximum-security forensic hospital in the United States. Accuracy in detecting deception was assessed before and after training via written transcripts. Results showed that training improved participants' accuracy, with accuracy rates increasing from 61% to 70%. Implications of the findings and recommendations for future research are discussed.
Keywords: United States; accuracy; adult; article; assessment criterion indicative of deception; clinical assessment tool; deception; deception detection; dept.psy; female; hospital; human; male; nursing staff; psychiatrist; psychologist; registered nurse; social worker; training; verbal cues; vocational education; workshop

A latent class analysis of DSM-IV alcohol use disorder criteria and binge drinking in undergraduates - Beseler, Cheryl L.; Taylor, Laura A.; Kraemer, Deborah T.; Leeman, Robert F. (Alcoholism-Clinical and Experimental Research, 2012)
Background: Adolescent and adult samples have shown that the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) abuse and dependence criteria lie on a continuum of alcohol problem severity, but information on criteria functioning in college students is lacking. Prior factor analyses in a college sample (Beseler et al., 2010) indicated that a 2-factor solution fit the data better than a single-factor solution after a binge drinking criterion was included. The second dimension may indicate a clustering of criteria related to excessive alcohol use in this college sample. Methods: The present study was an analysis of data from an anonymous, online survey of undergraduates (N = 361) that included items pertaining to the DSM-IV alcohol use disorder (AUD) diagnostic criteria and binge drinking. Latent class analysis (LCA) was used to determine whether the criteria best fit a categorical model, with and without a binge drinking criterion. Results: In an LCA including the AUD criteria only, a 3-class solution was the best fit. Binge drinking worsened the fit of the models. The largest class (class 1, n = 217) primarily endorsed tolerance (18.4%); none were alcohol dependent. The middle class (class 2, n = 114) endorsed primarily tolerance (81.6%) and drinking more than intended (74.6%); 34.2% met criteria for dependence. The smallest class (class 3, n = 30) endorsed all criteria with high probabilities (30 to 100%); all met criteria for dependence. Alcohol consumption patterns did not differ significantly between classes 2 and 3. Class 3 was characterized by higher levels on several variables thought to predict risk of alcohol-related problems (e. g., enhancement motives for drinking, impulsivity, and aggression). Conclusions: Two classes of heavy-drinking college students were identified, one of which appeared to be at higher risk than the other. The highest risk group may be less likely to “mature out” of high-risk drinking after college.
Keywords: Adolescent; Alcohol Typology; Alcohol Use Disorders; Alcohol-Related Disorders; College Students; Cross-Sectional Studies; Diagnostic and Statistical Manual of Mental Disorders; Ethanol; Female; Health Surveys; Humans; Impulsivity; Latent Class Analysis; Male; Risk Factors; Students; Universities; Young Adult; adult; aggression; alcohol consumption; alcohol use disorder criterion; alcoholism; article; binge drinking; clinical assessment tool; college student; controlled study; dept.psy; diagnostic and statistical manual of mental disorders; disease severity; drinking behavior; female; human; impulsiveness; major clinical study; male; motivation; priority journal; psychological model; undergraduate student

Scaffolding: Relationships among online quiz parameters and classroom exam scores - Anthis, Kristine; Adams, Lisa (Teaching of Psychology, 2012)
The current study examined relationships among online quiz parameters and students' classroom exam scores. The authors analyzed data from undergraduate courses across four semesters. The results revealed that regardless of the different parameters set for the online quizzes, the number of attempts that students made on quizzes was unrelated to their classroom exam scores, yet the amount of time they spent on quizzes was correlated negatively with their classroom exam scores. The results also revealed that students' scores on the online quizzes predicted their classroom exam scores, above and beyond the number of attempts, length of time allowed on quizzes, as well as their SAT Reading and SAT Math scores. The implications of these results are discussed subsequently. Future researchers may wish to provide empirical evidence on how not counting all of students' online quiz scores toward their final grade may influence students' quiz performance, given the anxiety that time limits can foster.
Keywords: attempts; dept.psy; exam scores; online quizzes; time limits

Effects of pre-trial response requirements on self-control choices by rats and pigeons. - Mazur, James E (Journal of the experimental analysis of behavior, 2012)
Parallel experiments with rats and pigeons examined whether the size of a pre-trial ratio requirement would affect choices in a self-control situation. In different conditions, either 1 response or 40 responses were required before each trial. In the first half of each experiment, an adjusting-ratio schedule was used, in which subjects could choose a fixed-ratio schedule leading to a small reinforcer, or an adjusting-ratio schedule leading to a larger reinforcer. The size of the adjusting ratio requirement was increased and decreased over trials based on the subject's responses, in order to estimate an indifference point-a ratio at which the two alternatives were chosen about equally often. The second half of each experiment used an adjusting-delay procedure-fixed and adjusting delays to the small and large reinforcers were used instead of ratio requirements. In some conditions, particularly with the reinforcer delays, the rats had consistently longer adjusting delays with the larger pre-trial ratios, reflecting a greater tendency to choose the larger, delayed reinforcer when more responding was required to reach the choice point. No consistent effects of the pre-trial ratio were found for the pigeons in any of the conditions. These results may indicate that rats are more sensitive to the long-term reinforcement rates of the two alternatives, or they may result from a shallower temporal discounting rate for rats than for pigeons, a difference that has been observed in previous studies.
Keywords: *Choice Behavior; *Conditioning, Operant; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Rats; Rats, Long-Evans; Reinforcement Schedule; animal; article; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; pigeons and doves; rat; reinforcement

Positive emotions, emotional intelligence, and successful experiential learning - Abe, Jo Ann A. (Personality and Individual Differences, 2011)
This study explored the role that positive emotions and emotional intelligence play in experiential learning. Students' field practicum journals were analyzed using the Linguistic Inquiry and Word Count Program (LIWC) and a measure of emotional intelligence was obtained using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT). Positive emotion words were robustly associated with almost all dimensions of supervisors' ratings of students' performance, but showed weak associations with students' ratings of perceived benefits associated with their practicum experiences. Overall El scores were correlated with several of the supervisor rating items and the Facilitating Thought and Managing Emotions subscales of the El were robustly correlated with many of the student rating items. This study thus yielded a more differentiated view of the role of positive emotions and emotional intelligence in adaptive functioning and underscored the importance of using multiple informants to assess a complex construct such as successful experiential learning. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Emotional intelligence; Experiential learning; LIWC; MSCEIT; Positive emotions; dept.psy

Functional activation for imitation of seen and heard speech - Irwin, Julia R.; Frost, Stephen J.; Mencl, W. Einar; Chen, Helen; Fowler, Carol A. (Journal of Neurolinguistics, 2011)
This study examined fMRI activation when perceivers either passively observed or observed and imitated matched or mismatched audiovisual (”McGurk”) speech stimuli. Greater activation was observed in the inferior frontal gyrus (IFG) overall for imitation than for perception of audiovisual speech and for imitation of the McGurk-type mismatched stimuli than matched audiovisual stimuli. This unique activation in the IFG during imitation of incongruent audiovisual speech may reflect activation associated with direct matching of incongruent auditory and visual stimuli or conflict between category responses. This study provides novel data about the underlying neurobiology of imitation and integration of AV speech. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Audiovisual; FMRI; Imitation; McGurk effect; Speech perception; Speech production; adult; article; auditory stimulation; brain function; brain region; controlled study; dept.psy; female; functional magnetic resonance imaging; human; human experiment; inferior frontal gyrus; male; priority journal; speech discrimination; speech perception; superior temporal gyrus; task performance; visual stimulation

Effects of neurofibromatosis type 1 on children's development - Haynes, Norris M.; Kirwan, Jacqueline R.; McCrohan, Kelly (Social Work in Public Health, 2011)
In-depth study of the human genome holds the potential to provide needed focus on genetic disorders that affect hundreds of thousands of children and significantly affect their development. Neurofibromatosis Type-1 (NF-1) is one of the most common genetic disorders that affect neurological, cognitive, social, and physical development. NF-1 affects all racial groups and both genders equally. NF-1 occurs in about 1 in 2,500 to 3,300 individuals in the population. The incidence rate at birth is about 0.0004 births in the United States and is growing in prevalence. Children with NF-1 experience a range of psychomotor and cognitive impairments that affect the quality of their social lives and their learning and academic achievements. Interventions to address the psychosocial and educational needs of children with NF-1 include a range of social and academic support services, which are most effective when they are comprehensive, involve a multidisciplinary team of educational and health experts, and include a focus on supporting and empowering family members to be effective caregivers. Efforts to address the needs of children with NF-1 and to provide adequate support to their families have significant policy implications for local, state, and federal officials.
Keywords: *Child Development; *Genome, Human; *Neurofibromatosis 1/px [Psychology]; *School Health Services; Adolescent; Adult; Aged; Child; Child Development; Child Welfare; Child, Preschool; Emotions; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Middle Aged; Neurofibromatosis; Neurofibromatosis 1; Neurofibromatosis 1/di [Diagnosis]; Neurofibromatosis 1/ep [Epidemiology]; Neurofibromatosis 1/ge [Genetics]; Patient Education as Topic; Power (Psychology); Power, Psychological; Prevalence; Risk Factors; School Health Services; Social Change; Social Work; United States; United States/ep [Epidemiology]; Young Adult; adolescent; adult; aged; article; behavior; birth rate; child; child development; child health; child welfare; cognition; dept.psy; disease incidence; disease prevalence; emotion; family empowerment; female; genetics; genome; heritability; human; human genome; infant; male; mental health; middle aged; neurofibromatosis; newborn; patient education; peer-reviewed; preschool child; prevalence; psychological aspect; psychology; risk factor; school health service; school psychologists; school-based interventions; social and emotional development; social change; social policy; social work

Augmenting acid with affective details to assess credibility - Ansarra, Ryan; Colwell, Kevin; Hiscock-Anisman, Cheryl; Hines, Amber; Fleck, Roland; Cole, Lindsey; Belarde, Delyana (European Journal of Psychology Applied to Legal Context, 2011)
There is a need within the criminal justice systems of many countries to create a valid and applicable system of investigative interviewing and credibility assessment. The present study assesses the general validity one such system, called Assessment Criteria Indicative of Deception (ACID). ACID comprises interviewing strategies that facilitate the detection of deception and content criteria that highlight differences in verbal behavior. Sixty university undergraduates performed a staged theft under time pressure and with incentives designed to increase external validity. The participants were interviewed and assessed using the ACID procedure. Half of them were instructed to answer honestly and the other half to deny his/her participation in the theft. Results showed that honest statements were longer, more vividly detailed, and more spontaneously structured than deceptive statements. Also, the addition of affective details as a dependent measure significantly improved the ACID system. Overall, 48 of 60 statements were accurately classified (26 of 30 honest statements and 22 of 30 deceptive statements). The ACID procedure was effective and benefited from the addition of affective details. The strengths and weaknesses of this study are discussed in light of basic research into deception and potential forensic application.
Keywords: Content analysis; Credibility assessment; Detecting deception; Investigative interviewing; Testimony; dept.psy; ⛔ No DOI found

Changes in alan greenspan's language use across the economic cycle: A text analysis of his testimonies and speeches - Abe, Jo Ann A. (Journal of Language and Social Psychology, 2011)
This study examined changes in Alan Greenspan's language use across the economic cycle by analyzing his testimonies and speeches using the Linguistic Inquiry and Word Count Program (LIWC), which is a widely used text analysis program. Consistent with expectations, Greenspan showed an increase in the composite measure of psychological distancing as well as a decline in the measure of cognitive complexity between the economic expansion and downturn periods. Interestingly, these patterns of changes became more pronounced during the purported economic recovery period. In contrast to the measures of psychological distancing and cognitive complexity, the measure of emotionality remained relatively stable across the economic cycle.
Keywords: Greenspan; LIWC; cognitive complexity; computerized text analysis; dept.psy; peer-reviewed; psychological distancing

Effect of night smoking, sleep disturbance, and their co-occurrence on smoking outcomes - Peters, Erica N.; Fucito, Lisa M.; Novosad, Claire; Toll, Benjamin A.; O'Malley, Stephanie S. (Psychology of Addictive Behaviors, 2011)
Recent evidence suggests that smoking during the night is an indicator of nicotine dependence and predicts smoking cessation failure. Night smokers are likely to experience disturbance to their sleep cycle when they wake to smoke, but we are not aware of the prevalence of night smokers' self-reported sleep disturbance. Because sleep disturbance also predicts smoking cessation failure, we examined how the pre-cessation risk factors of night smoking and sleep disturbance, and their co-occurrence, predict smoking cessation failure in a 6-week double-blind randomized controlled trial examining whether naltrexone augments the efficacy of the nicotine patch (O'Malley et al., 2006). Smokers (N = 385) completed the Pittsburgh Sleep Quality Index (Buysse, Reynolds, Monk, Berman, & Kupfer, 1989) and a single item of waking at night to smoke pre-cessation. Smoking status was determined at weeks 1, 6, 24, and 48 weeks after quitting. The two main findings were: (a) night smokers reported significantly greater sleep disturbance than nonnight smokers; and (b) smokers with co-occurring night smoking and sleep disturbance experienced significantly greater risk for smoking than smokers with neither risk factor. Results suggest that individuals who both wake during the night to smoke and report clinically-significant sleep disturbance represent a high-risk group of smokers. Future smoking cessation treatment might incorporate strategies related to managing these smokers' sleep habits and physiological dependence on nicotine in order to bolster their cessation outcomes.
Keywords: Adult; Double-Blind Method; Female; Humans; Male; Middle Aged; Night smoking; Outcome predictors; Pittsburgh Sleep Quality Index; Prevalence; Self Report; Sleep Disorders; Sleep disturbance; Smoking; Smoking Cessation; Smoking cessation; Tobacco Use Disorder; Treatment Outcome; adult; article; cigarette smoking; comorbidity; controlled study; dept.psy; double blind procedure; drug dose comparison; female; high risk patient; human; major clinical study; male; naltrexone; named inventories, questionnaires and rating scales; nicotine patch; night; placebo; prediction; randomized controlled trial; risk factor; sleep disorder; smoking cessation; smoking habit; tobacco dependence; treatment failure; wakefulness

AVSP - Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T.; Kroos, Christian; Irwin, Julia (2011)
Keywords: dept.psy

Effects of time between trials on rats' and pigeons' choices with probabilistic delayed reinforcers. - Mazur, James E; Biondi, Dawn R (Journal of the Experimental Analysis of Behavior, 2011)
Parallel experiments with rats and pigeons examined reasons for previous findings that in choices with probabilistic delayed reinforcers, rats' choices were affected by the time between trials whereas pigeons' choices were not. In both experiments, the animals chose between a standard alternative and an adjusting alternative. A choice of the standard alternative led to a short delay (1 s or 3 s), and then food might or might not be delivered. If food was not delivered, there was an "interlink interval," and then the animal was forced to continue to select the standard alternative until food was delivered. A choice of the adjusting alternative always led to food after a delay that was systematically increased and decreased over trials to estimate an indifference point--a delay at which the two alternatives were chosen about equally often. Under these conditions, the indifference points for both rats and pigeons increased as the interlink interval increased from 0 s to 20 s, indicating decreased preference for the probabilistic reinforcer with longer time between trials. The indifference points from both rats and pigeons were well described by the hyperbolic-decay model. In the last phase of each experiment, the animals were not forced to continue selecting the standard alternative if food was not delivered. Under these conditions, rats' choices were affected by the time between trials whereas pigeons' choices were not, replicating results of previous studies. The differences between the behavior of rats and pigeons appears to be the result of procedural details, not a fundamental difference in how these two species make choices with probabilistic delayed reinforcers.
Keywords: *Choice Behavior; *Memory, Short-Term; *Probability Learning; *Reinforcement Schedule; Animals; Choice Behavior; Columbidae; Conditioning, Operant; Long Evans rat; Male; Memory, Short-Term; Motivation; Probability Learning; Psychomotor Performance; Rats; Rats, Long-Evans; Reinforcement Schedule; Species Specificity; Time Perception; animal; article; decision making; dept.psy; instrumental conditioning; learning; male; motivation; peer-reviewed; pigeons and doves; psychomotor performance; rat; reinforcement; short term memory; species difference; time perception

Is it the clicker, or is it the question? Untangling the effects of student response system use - Anthis, Kristine (Teaching of Psychology, 2011)
Previous research on the effectiveness of clickers has found their use to be positively associated with exam scores but not without methodological issues that hinder the conclusions that can be drawn. To address these limitations, the current studies isolated the effects of clickers from the effects of questions presented with clickers. Study 1 showed that students who did not use clickers to respond to questions but raised their hands performed better on exams than students who saw the same questions and responded with clickers. Study 2 found no relationship between clicker use and exam scores, which suggests that prior research claims about the effectiveness of clickers may have been premature given that clicker use was confounded with question use in those studies. Suggestions for future research are also provided.
Keywords: SRS; clickers; dept.psy; metacognition

Do infants detect A→V articulator congruency for non-native click consonants? - Best, Catherine T; Kroos, Christian; Irwin, Julia (Proceedings of the International Conference on Audio-Visual Speech Processing (AVSP2011), Aug 31 - Sep 3, 2011, Volterra, Italy, 2011)
Keywords: dept.psy; ⛔ No DOI found

Assessing feigned cognitive impairment in defendants hospitalized for competency restoration: further validation of the TOMI - Colwell, Lori H.; Colwell, Kevin (Journal of Forensic Psychology Practice, 2011)
Valid screens for feigned cognitive impairment are a fundamental component of any forensic assessment. The TOMI is a verbally administered, two-alternative forced-choice screen for feigned cognitive impairment in competence to stand trial (CST) evaluations. The present study provided further validation for the use of this tool in a sample of 82 forensic inpatients, the second investigation of the TOMI in a real-world, psycholegal context. Using three independent external criteria-the Test of Memory Malingering (TOMM) Trial 2 score, TOMM Retention Trial score, and a clinical treatment team decision-and these combined criteria-the Legal Knowledge scale (TOMI-L) evidenced high levels of sensitivity and specificity and excellent negative predictive power (NPP). The General Knowledge scale (TOMI-G) demonstrated poor sensitivity but high specificity and NPP. The authors discuss the utility of both scales in guiding and streamlining more thorough assessments of response styles in CST evaluations.
Keywords: Competency; Forensic assessment; Legal Knowledge scale; Malingering; Test of Malingered Incompetence; Twoalternative forced-choice; adult; analytic method; article; clinical assessment tool; clinical decision making; clinical treatment team decision; cognitive defect; competence; dept.psy; forensic medicine; human; legal aspect; major clinical study; male; psychological aspect; sensitivity and specificity; validation process

Can children with autism spectrum disorders “Hear” a speaking face? - Irwin, Julia; Tornatore, Lauren A; Brancazio, Lawrence; Whalen, D H (Child Development, 2011)
This study used eye-tracking methodology to assess audiovisual speech perception in 26 children ranging in age from 5 to 15 years, half with autism spectrum disorders (ASD) and half with typical development. Given the characteristic reduction in gaze to the faces of others in children with ASD, it was hypothesized that they would show reduced influence of visual information on heard speech. Responses were compared on a set of auditory, visual, and audiovisual speech perception tasks. Even when fixated on the face of the speaker, children with ASD were less visually influenced than typical development controls. This indicates fundamental differences in the processing of audiovisual speech in children with ASD, which may contribute to their language and communication impairments.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Communication; Female; Humans; Language Development Disorders; Lipreading; Male; Pattern Recognition, Visual; Perceptual Masking; Reference Values; Speech Perception; Verbal Behavior; adolescent; article; autism; child; dept.hls; dept.psy; female; human; interpersonal communication; language disability; lip reading; male; pattern recognition; perception; preschool child; psychological aspect; reference value; speech perception; verbal behavior

Effects of playing wii on well-being in the elderly: physical activity, loneliness, and mood - Kahlbaugh, Patricia E; Sperandio, Amanda J; Carlson, Ashley L; Hauselt, Jerry (Activities, Adaptation & Aging, 2011)
Effects of compensatory strategies offered by Wii technology on physical activity, loneliness, and mood are investigated. Thirty-five individuals (M = 82 years) were randomly assigned to either playing Wii or watching television with a partner for 10 weeks. Physical activity, loneliness, mood, life satisfaction, and health were assessed. The elderly playing Wii had lower loneliness and a pattern of greater positive mood compared to the television group. No differences in life satisfaction or physical activity were found, but loneliness predicted positive mood, and positive mood predicted physical activity. This investigation points to the benefits of using Wii for well-being, particularly social connection and enjoyment. © 2011 Copyright Taylor and Francis Group, LLC.
Keywords: dept.psy; integrative game playing; loneliness; mood; older adult recreation; well-being

The effect of playing the wii on loneliness and mood in the elderly - Kahlbaugh, P. E.; Sperandio, A. J.; Carlson, A. (Gerontologist, 2010)
Keywords: dept.psy; peer-reviewed; ⛔ No DOI found

Distinguishing truthful from invented accounts using reality monitoring criteria - Memon, Amina; Fraser, Joanne; Colwell, Kevin; Odinot, Geralda; Mastroberardino, Serena (Legal and Criminological Psychology, 2010)
Purpose. Previous research has suggested that true and invented memories can be distinguished between using the reality monitoring criteria. Two different coding schemes were used to examine the correct classification of reports as truthful or deceptive on the basis of individual reality-monitoring (RM) criteria. Method. Drawing upon the RM framework the present experiment examined transcripts of verbal accounts of eyewitnesses to a staged event or made up details about the incident. The statements were elicited during a face-to-face cognitive interview (CI) and were analysed by coders trained in the identification of criteria indicative of self-experienced and invented accounts (referred to here as Version 1) and a similar coding method (referred to here as Version 2). Results. A distinction was made between `external memories' (affective, perceptual, and contextual details) and `internal' memories (cognitive operations). For Version 1, the results indicated a higher number of contextual and external details in the descriptions of experienced events and as is commonly found in the deception literature, truthful accounts were longer. For Version 2, temporal and auditory details were more frequent in true accounts. Contrary to prediction, there were also more references to cognitive operations in true accounts. Conclusions. Any forensic application of RM should consider how external factors (characteristics of the event, motivation to deceive, and questioning style) influence the presence of RM criteria.
Keywords: adult; article; coding; cognition; controlled study; dept.psy; female; human; interview; major clinical study; male; memory; monitoring; priority journal; questionnaire; reality monitoring; self concept; verbal communication; witness

Distributed versus exclusive preference in discrete-trial choice. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2010)
Two experiments on discrete-trial choice examined the conditions under which pigeons would exhibit exclusive preference for the better of two alternatives as opposed to distributed preference (making some choices for each alternative). In Experiment 1, pigeons chose between red and green response keys that delivered food after delays of different durations, and in Experiment 2 they chose between red and green keys that delivered food with different probabilities. Some conditions of Experiment 1 had fixed delays to food and other conditions had variable delays. In both experiments, exclusive or nearly exclusive preference for the better alternative was found in some conditions, but distributed preference was found in other conditions, especially in Experiment 2 when key location varied randomly over trials. The results were used to evaluate several different theories about discrete-trial choice. The results suggest that exclusive preference for one alternative is a frequent outcome in discrete-trial choice. When distributed preference does occur, it is not the result of inherent tendencies to sample alternatives or to match response percentages to the values of the alternatives. Rather, distributed preference may occur when two factors (such as reinforcer delay and position bias) compete for the control of choice, or when the consequences for the two alternatives are similar and difficult to discriminate.
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning, Operant/ph [Physiology]; *Reinforcement Schedule; *Reinforcement, Psychology; Animals; Choice Behavior; Columba; Columbidae; Conditioning, Operant; Discrete-trial choice; Exclusive preference; Male; Pigeons; Probability; Reaction Time; Reaction Time/ph [Physiology]; Reinforcement (Psychology); Reinforcement Schedule; Reinforcer delay; Time Factors; animal; article; decision making; dept.psy; instrumental conditioning; male; physiology; pigeons and doves; probability; reaction time; reinforcement; time

Impression management strategies of deceivers and honest reporters in an investigative interview - Hines, Amber; Colwell, Kevin; Hiscock-Anisman, Cheryl; Garrett, Erika; Ansarra, Ryan; Montalvo, Larissa (European Journal of Psychology Applied to Legal Context, 2010)
Understanding the subjective experience of respondents attempting to convince an investigator will enhance our theoretical knowledge of deception and improve assessment techniques. Discrepancies between respondents' understanding and actual credibility criteria are especially important. Sixty-six participants engaged in a small crime, and were interviewed following a week's preparation. All were provided incentive for convincing the interviewer of the veracity of their statement. Thirty-two were honestly reporting the theft, and thirty-four were responding to avoid being found guilty. After a Reality Interview (a derivative of the Cognitive Interview), participants were asked to describe what was important in convincing the interviewer through open-ended and Liken-type questions. These strategies of impression management are presented here. The basic task of convincing appeared similar for both groups, with participants focused on providing clear and careful stories without contradictions rather than attempting to provide vivid and spontaneously-constructed statements. Deceivers attached more importance to: I) preparing in advance, 2) monitoring and controlling information, and 3) maintaining eye contact. Honest respondents were more concerned with providing correct peripheral detail. Importantly, both groups were reporting much more similarity than difference, and the strategies described are not likely to succeed against verbal content analysis.
Keywords: Credibility; Deception; Interrogation; Testimony; Verbal communication; dept.psy; ⛔ No DOI found

Book Review: Elaine f. weiss, fruits of victory: the woman's land army of america in the great war - Irwin, Julia F (First World War Studies, 2010)
Keywords: book.review; dept.psy

Seeing to hear? Patterns of gaze to speaking faces in children with autism spectrum disorders. - Irwin, Julia R; Brancazio, Lawrence (Frontiers in Psychology, 2014)
Using eye-tracking methodology, gaze to a speaking face was compared in a group of children with autism spectrum disorders (ASD) and a group with typical development (TD). Patterns of gaze were observed under three conditions: audiovisual (AV) speech in auditory noise, visual only speech and an AV non-face, non-speech control. Children with ASD looked less to the face of the speaker and fixated less on the speakers' mouth than TD controls. No differences in gaze were reported for the non-face, non-speech control task. Since the mouth holds much of the articulatory information available on the face, these findings suggest that children with ASD may have reduced access to critical linguistic information. This reduced access to visible articulatory information could be a contributor to the communication and language problems exhibited by children with ASD.
Keywords: Audiovisual speech perception; Autism spectrum disorders; Communication development; Eyetracking; Lipreading; Speech in noise; dept.hls; dept.hms; dept.psy; peer-reviewed

Development of an audiovisual speech perception app for children with autism spectrum disorders - Irwin, Julia; Preston, Jonathan; Brancazio, Lawrence; D'Angelo, Michael; Turcios, Jacqueline (Clinical Linguistics & Phonetics, 2015)
Perception of spoken language requires attention to acoustic as well as visible phonetic information. This article reviews the known differences in audiovisual speech perception in children with autism spectrum disorders (ASD) and specifies the need for interventions that address this construct. Elements of an audiovisual training program are described. This researcher-developed program delivered via an iPad app presents natural speech in the context of increasing noise, but supported with a speaking face. Children are cued to attend to visible articulatory information to assist in perception of the spoken words. Data from four children with ASD ages 8-10 are presented showing that the children improved their performance on an untrained auditory speech-in-noise task.
Keywords: Attention; Audiovisual Aids; Audiovisual app; Autism spectrum disorder; Child; Child Development Disorders, Pervasive; Comprehension; Humans; Lipreading; Male; Mobile Applications; Pattern Recognition, Visual; Phonetics; Semantics; Speech Perception; Speech perception; attention; audiovisual aid; child; comprehension; dept.cmd; dept.hls; dept.psy; human; lip reading; male; mobile application; pattern recognition; phonetics; psychology; semantics; speech perception

Neurophysiology of speech differences in childhood apraxia of speech - Preston, Jonathan L; Molfese, Peter J; Gumkowski, Nina; Sorcinelli, Andrea; Harwood, Vanessa; Irwin, Julia; Landi, Nicole (Developmental Neuropsychology, 2014)
Event-related potentials (ERPs) were recorded during a picture naming task of simple and complex words in children with typical speech and with childhood apraxia of speech (CAS). Results reveal reduced amplitude prior to speaking complex (multisyllabic) words relative to simple (monosyllabic) words for the CAS group over the right hemisphere during a time window thought to reflect phonological encoding of word forms. Group differences were also observed prior to production of spoken tokens regardless of word complexity during a time window just prior to speech onset (thought to reflect motor planning/programming). Results suggest differences in pre-speech neurolinguistic processes.
Keywords: Adolescent; Apraxias; Child; Evoked Potentials; Female; Humans; Linguistics; Male; Neurophysiology; Speech; adolescent; apraxia; article; child; comparative study; dept.cmd; dept.psy; evoked response; female; human; linguistics; male; neurophysiology; pathophysiology; physiology; speech

Can color-coded word-families flashcards facilitate word recognition in kindergarteners? - Durwin, Cheryl C.; Moore, Dina (Reading Improvement, 2019)
Three novel experiments investigated the effectiveness of color-coded word-families flashcards for facilitating kindergarteners' word recognition skills. Flashcards were constructed with the rime of the word family (vowel and remaining consonant sounds) printed in black ink, indicating that words with this spelling pattern sound the same, and the onsets (initial consonant sounds) shown in different colors, indicating the sound changes from word to word. All experiments involved preand post-testing on word recognition and phonological awareness and random assignment to intervention or control conditions. The length of intervention and type of control condition differed among experiments. Results suggested that word-families may facilitate word recognition skill development and that factors such as amount of practice, phonological awareness, and socioeconomic status impact the efficacy of the intervention.
Keywords: dept.psy; early literacy; elementary schools; peer-reviewed; phonological awareness; reading instructors; reading intervention; ⛔ No DOI found

Experimentally induced variation in neuroendocrine processes affects male reproductive behaviour, sperm characteristics and social interactions - Nugent, Bridget M.; Stiver, Kelly A.; Hofmann, Hans A.; Alonzo, Suzanne H. (Molecular Ecology, 2019)
While extensive research has focused on how social interactions evolve, the fitness consequences of the neuroendocrine mechanisms underlying these interactions have rarely been documented, especially in the wild. Here, we measure how the neuroendocrine mechanisms underlying male behaviour affect mating success and sperm competition in the ocellated wrasse (Symphodus ocellatus). In this species, males exhibit three alternative reproductive types. “Nesting males” provide parental care, defend territories and form cooperative associations with unrelated “satellites,” who cheat by sneaking fertilizations but help by reducing sperm competition from “sneakers” who do not cooperate or provide care. To measure the fitness consequences of the mechanisms underlying these social interactions, we used “phenotypic engineering” that involved administering an androgen receptor antagonist (flutamide) to wild, free-living fish. Nesting males treated with flutamide shifted their aggression from sneakers to satellite males and experienced decreased submissiveness by sneaker males (which correlated with decreased nesting male mating success). The preoptic area (POA), a region controlling male reproductive behaviours, exhibited dramatic down-regulation of androgen receptor (AR) and vasotocin 1a receptor (V1aR) mRNA following experimental manipulation of androgen signalling. We did not find a direct effect of the manipulation on male mating success, paternity or larval production. However, variation in neuroendocrine mechanisms generated by the experimental manipulation was significantly correlated with changes in behaviour and mating success: V1aR expression was negatively correlated with satellite-directed aggression, and expression of its ligand arginine vasotocin (AVT) was positively correlated with courtship and mating success, thus revealing the potential for sexual selection on these mechanisms. © 2018 John Wiley & Sons Ltd
Keywords: 11-ketotestosterone; Androgen Receptor Antagonists; Animals; Brain; Female; Flutamide; Male; Neurosecretory Systems; Perciformes; RNA, Messenger; Receptors, Androgen; Reproduction; Sexual Behavior, Animal; Social Behavior; Spermatozoa; Testosterone; alternative reproductive tactics; androgen receptor; androgen receptor antagonist; androgens; animal; brain; dept.psy; drug effect; female; flutamide; genetics; male; messenger RNA; metabolism; neuroendocrine; neuroendocrine system; peer-reviewed; physiology; reproduction; sexual behavior; sexual selection; social behavior; social behaviour; spermatozoon; teleosts; testosterone

Neuropeptide manipulation has behavioural and cascading fitness consequences in wild-living fish - Stiver, Kelly A.; Marsh-Rollo, Susan E.; Alonzo, Suzanne H. (Animal Behaviour, 2019)
Due to the difficulty of simultaneously assessing variation in individual physiology, behaviour and fitness, we often know little about the mechanistic basis of life-history trade-offs and fitness variation. It is similarly challenging to examine how physiological variation in one individual has cascading fitness consequences for others in the social environment. Using a wild-living fish (ocellated wrasse, Symphodus ocellatus), we manipulated a neuropeptide pathway associated with courtship, aggression and parental care in vertebrates (arginine vasotocin, AVT) and directly examined the behavioural and fitness consequences. Nesting males injected with the AVT antagonist increased their paternal care, resulting in increased hatching of offspring and increased reproductive success of all individuals that mated at his nest. By directly examining physiology, behaviour and reproductive success, we revealed how a small change in individual physiology has clear and direct fitness consequences for multiple individuals. © 2019 The Association for the Study of Animal Behaviour
Keywords: Symphodus ocellatus; Vertebrata; arginine vasotocin; behavioral response; dept.psy; fitness; fitness consequences; life history; nonapeptide; parental care; parental investment; paternal care; peer-reviewed; peptide; phenotype; phenotypic engineering; physiological manipulation; physiology; proximate mechanisms; reproductive cost; reproductive investment; reproductive success; trade-off; trade-offs; wild population

The efficacy of free-recall, cognitive load, and closed-ended questions when children are asked to falsely testify about a crime - Wyman, Joshua; Foster, Ida; Crossman, Angela; Colwell, Kevin; Talwar, Victoria (Applied Cognitive Psychology, 2019)
The current study evaluated the benefits of free-recall, cognitive load, and closed-ended questions on children's (ages 6 to 11; N = 147) true and false eyewitness disclosures. Children witnessed an experimenter find a stranger's wallet and were then asked to make a false denial, false accusation, true denial, or true accusation regarding an alleged theft. Overall, the free-recall question resulted in longer, more forthcoming and more detailed disclosures from older children and those who made a truthful accusation; however, children under the age of 9 and lie-tellers mostly relied on the closed-ended questions to discuss the theft. Although the cognitive load questions resulted in newly recalled information, there were no significant narrative differences between true and false statements on these questions. These findings suggest that forensic professionals should consider a child's developmental level, statement veracity, and disclosure-type (denial vs. accusation) when examining the efficacy of these commonly used questioning strategies.
Keywords: article; child; children; cognitive load; dept.psy; drug efficacy; eyewitness reports; false reports; female; free-recall; human; human experiment; major clinical study; male; narrative; peer-reviewed; recall; theft; witness

The language of wisdom understood through an analysis of wise quotes - DeFrank, Melanie; Bivona, Marissa; Chiaraluce, Brianna; Kahlbaugh, Patricia (Journal of Language and Social Psychology, 2019)
Wise quotes carry advice about how to navigate life's difficult decisions or feelings, allowing cultures to pass wisdom through generations. Qualities of wisdom have been identified by careful examination of wise individuals. Similarly, wise sayings and quotations can be analyzed and interpreted as emblematic of cultural beliefs about wisdom. The present research examines thematic and linguistic qualities of 157 wise quotes nominated as wise by 194 undergraduates. Thematic analysis of wise quotes centered on five dimensions of wisdom: Humor, Emotion, Review, Openness and Experience. Humor and Emotion were found to be the least represented while Review and Experience were the most represented. Linguistic analysis compared strong (n = 101) versus weak (n = 56) wise quotes and found that strong wise quotes were more linguistically complex and less likely to use the first-person pronouns. Analyzing the language of wisdom through quotes can provide additional insight into cultural representations of wisdom.
Keywords: adult; article; communicating wisdom; controlled study; dept.psy; female; human; human experiment; humor; language; major clinical study; male; peer-reviewed; quotes; text analysis; thematic analysis; wisdom

Tests of an indifference rule in variable-delay and double-reward choice procedures with humans - McKerchar, Todd L.; Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2019)
Four hundred and fifty participants were recruited from Amazon Mechanical Turk across 3 experiments to test the predictions of a hyperbolic discounting equation in accounting for human choices involving variable delays or multiple rewards (Mazur, 1984, 1986). In Experiment 1, participants made hypothetical choices between 2 monetary alternatives, 1 consisting of a fixed delay and another consisting of 2 delays of equal probability (i.e., a variable-delay procedure). In Experiment 2, participants made hypothetical monetary choices between a single, immediate reward and 2 rewards, 1 immediate and 1 delayed (i.e., a double-reward procedure). Experiment 3 also used a double-reward procedure, but with 2 delayed rewards. Participants in all 3 experiments also completed a standard delay-discounting task. Finally, 3 reward amounts were tested in each type of task ($100, $1000, and $5000). In the double-reward conditions (Experiments 2 and 3), the results were in good qualitative and quantitative agreement with Mazur's model (1984, 1986). In contrast, when participants made choices involving variable delays (Experiment 1), there was relatively poor qualitative and quantitative agreement with this model. These results, along with our previous findings, suggest the structure of questions in hypothetical tasks with humans can be a strong determinant of the choice pattern.
Keywords: Adult; Choice Behavior; Delay Discounting; Female; Humans; Male; Models, Psychological; Probability; Reward; adult; choice; decision making; delay discounting; dept.psy; female; human; humans; hyperbolic discounting; male; mathematical model; peer-reviewed; probability; psychological model; reward

Using the reality interview improves the accuracy of the Criteria‐Based content analysis and reality monitoring - Bogaard, Glynis; Colwell, Kevin; Crans, Samantha (Applied Cognitive Psychology, 2019)
Active interviewing approaches can exploit the verbal differences between truthtellers and liars, thus improving detecting deception. One such method is the Reality Interview (RI) aimed to facilitate recall from truthtellers, while increasing the difficulty for liars. This study investigated whether the RI could improve the diagnostic accuracy of the Reality Monitoring and the Criteria-Based Content Analysis. Liars and truthtellers were either asked to freely recall an event or interviewed with the RI. As hypothesized, the RI improved the discriminability of Reality Monitoring and Criteria-Based Content Analysis over Free Recall. Honest responses were longer, and the RI increased the word count difference between honest and false statements. However, after correcting for word count, results were no longer significant, showing its importance for deception detection. Nonetheless, the RI increased verbal differences between truthtellers and liars, demonstrating that using the RI with verbal credibility assessment tools is a powerful combination for investigative interviewing. © 2019 The Authors Applied Cognitive Psychology Published by John Wiley & Sons Ltd.
Keywords: Criteria-Based Content Analysis; Reality Interview; Reality Monitoring; article; content analysis; credibility assessment; deception; deception detection; dept.psy; diagnostic accuracy; diagnostic test accuracy study; human; human experiment; interview; monitoring; peer-reviewed; recall

Social anxiety and employment interviews: does nonverbal feedback differentially predict cortisol and performance? - Budnick, Christopher J.; Anderson, Eden M.; Santuzzi, Alecia M.; Grippo, Angela J.; Matuszewich, Leslie (Anxiety Stress and Coping, 2019)
Background & Objectives: Interviewers often provide positive nonverbal feedback to reduce interviewees' anxiety. Socially anxious individuals typically harbor negative self-views discrepant with positive feedback. We examined whether nonverbal feedback and social anxiety jointly influence cortisol responses to, and performance during, interviews. Design: An experimental between-subjects design randomly assigned participants to feedback condition. Methods: Undergraduate students (N = 130) provided saliva and completed social anxiety, interview anxiety, and affective measures before a simulated interview. Following a standardized script, a confederate interviewer provided positive, ambiguous, or negative nonverbal feedback. Participants then provided saliva and completed self-focused attention and self-awareness measures. Confederate interviewers and an external rater evaluated participants' anxiety displays, assertive behavior, and performance. Results: Positive feedback decreased cortisol and improved performance for low social anxiety participants. Socially anxious participants exhibited higher cortisol but did not exhibit significant differences in performance after positive compared to negative feedback. Conclusions: Consistent with previous findings, positive feedback did not benefit socially anxious interviewees. Positive feedback increased physiological arousal relative to negative feedback but did not hinder performance among people high in social anxiety. These results provide novel information about the interactive influence of social anxiety and nonverbal interviewer feedback on arousal, self-focus, and interview performance.
Keywords: Anxiety; Arousal; Attention; Feedback; Female; Humans; Hydrocortisone; Interviews as Topic; Job Application; Male; Saliva; Social anxiety; anxiety; arousal; attention; chemistry; controlled study; cortisol; dept.psy; feedback system; female; human; hydrocortisone; interview; interview anxiety; interviews; job finding; male; pathophysiology; peer-reviewed; psychology; randomized controlled trial; saliva; self-verification

Restraint stress exacerbates cell degeneration induced by acute binge ethanol in the adolescent, but not in the adult or middle-aged, brain - Fernandez, Macarena Soledad; de Olmos, Soledad; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2019)
Restraint stress (RS) induces neurotoxicity in the hippocampus, yet most of the studies have employed protracted RS (i.e., = 21 days). Binge ethanol can induce brain toxicity, an effect affected by age. It could be postulated that RS may facilitate ethanol-induced neurotoxicity, perhaps to a greater extent in adolescent vs. older subjects. We analyzed whether adolescent, adult or middle-aged male rats exposed to five episodes of RS followed, 72h later, by binge ethanol (i.e., two administrations of 2.5 g/kg ethanol) exhibited hippocampal neurotoxicity. Adolescents, but not adult or middle-aged rats, exhibited sensitivity to the neurotoxic effects of ethanol at dorsal CA2, ventral CA3 and ventral DG, and a neurotoxic effect of stress at dorsal CA1. Moreover, the combination of ethanol and stress exerted a synergistic effect upon cell degeneration at ventral CA1 and CA2, which was restricted to adolescents. Ethanol also increased cell degeneration, irrespective of age or stress, in dorsal CA3 and in dorsal DG; and ethanol and stress had, across all ages, a synergistic effect upon cell degeneration at the dorsal CA1. The greater neurotoxic response of adolescents to ethanol, stress, or ethanol+stress can put them at risk for the development of alcohol problems. Copyright © 2019 Elsevier B.V. All rights reserved.
Keywords: *Age Factors; *Binge Drinking/pp [Physiopathology]; *Ethanol/ae [Adverse Effects]; Adolescent; Adult rats; Age Factors; Animals; Article; Binge Drinking; Binge Drinking/me [Metabolism]; Brain; Brain/de [Drug Effects]; Dentate Gyrus; Dentate Gyrus/de [Drug Effects]; Ethanol; Ethanol/pd [Pharmacology]; Hippocampus; Hippocampus/de [Drug Effects]; Male; Middle-Aged rats; Neurotoxicity; Rats; Rats, Wistar; Restraint, Physical; Wistar rat; adolescent; adult; adult animal; age; alcohol; animal; animal behavior; animal cell; animal experiment; animal model; animal tissue; binge drinking; brain; controlled study; dentate gyrus; dept.psy; dorsal hippocampus; drinking behavior; drug effect; exercise; hippocampal CA1 region; hippocampal CA2 region; hippocampal CA3 region; hippocampus; immobilization stress; male; metabolism; middle aged; nerve cell degeneration; neurotoxicity; nonhuman; pathophysiology; peer-reviewed; priority journal; rat; sensitivity analysis; underage drinking; ventral dentate gyrus; ventral hippocampus

Offspring of male rats exposed to binge alcohol exhibit heightened ethanol intake at infancy and alterations in T-maze performance. - Hollander, Jessica; McNivens, Megan; Pautassi, Ricardo M; Nizhnikov, Michael E (Alcohol, 2019)
Alcohol use is associated with a variety of negative consequences, including heightened likelihood of cognitive impairment, proclivity to alcohol use disorders (AUD), and alterations in the drinker's offspring. Children and rodents exposed to alcohol during pregnancy, or those whose fathers consumed alcohol prior to mating, often exhibit neurodevelopmental, physiological, and behavioral deficits. The present study assessed cognitive function and alcohol intake in male and female rats that were offspring of alcohol-exposed fathers. Adult male rats were exposed to alcohol or vehicle (0.0 or 2.0 g/kg, respectively; twice daily for 2 days followed by a rest day, for a total of eight alcohol or vehicle exposure days), or were left untreated and then mated with non-manipulated females. The offspring were assessed for alcohol intake, via intraoral infusion, followed by cognitive assessment via an alternating T-maze task. The results indicated that paternal ethanol exposure, prior to breeding, resulted in offspring that consumed significantly more ethanol than vehicle or untreated controls. Furthermore, the offspring of alcohol-exposed fathers exhibited a significant failure to initiate and complete the T-maze performance tests. Although, when they did engage in the tests they performed at the level of controls (i.e., 80% correct). The present results add to a growing body of literature suggesting that paternal pre-conception alcohol exposure can have deleterious effects on the offspring. Copyright © 2018 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/px [Psychology]; *Binge Drinking/px [Psychology]; *Fathers/px [Psychology]; *Maze Learning/de [Drug Effects]; *Prenatal Exposure Delayed Effects/px [Psychology]; Alcohol Drinking; Alcohol intake; Animals; Article; Binge Drinking; Fathers; Female; Male; Maze Learning; Paternal alcohol exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats; T-maze; T-maze test; adult; alcohol; alcohol consumption; animal; animal experiment; binge drinking; cognition; controlled study; dept.psy; drinking behavior; drug effect; father; female; male; maze test; nonhuman; paternal exposure; peer-reviewed; pregnancy; prenatal exposure; psychology; rat

Language choice matters: when profanity affects how people are judged - DeFrank, Melanie; Kahlbaugh, Patricia E (Journal of Language and Social Psychology, 2019)
Swearing is prevalent in our society, but the influence of such language choices on judgments of others is not well understood. This study examines how the composition of conversational dyads, speaker's gender, and use of profanity influence impressions. Participants (N = 138) were randomly assigned to read two conversations and rate target speakers (one male, one female). The conversations had neither, one, or both speakers using profanity and consisted of same- or mixed-gender dyads. The result is a 2 (target speaker, male/female) x 2 (dyad composition) x 3 (profanity) mixed design with speaker gender as the repeated measure. Speakers using profanity had poorer impression ratings on several variables, including overall impression, intelligence, and trustworthiness. Speakers swearing in mixed-gender dyads were rated as less sociable, and males swearing in mixed-gender dyads were rated as more offensive. Language choices matter, and more research is needed to understand the unconscious biases held against those who use profanity.
Keywords: adult; article; controlled study; conversation; dept.psy; ego development; female; gender; human; human experiment; impression formation; intelligence; language; major clinical study; male; peer-reviewed; profanity; randomized controlled trial

A comparison of different investigative interviewing techniques in generating differential recall enhancement and detecting deception - De Rosa, Jacob; Hiscockanisman, Cheryl; Blythe, Adam; Bogaard, Glynis; Hally, Ashley; Colwell, Kevin (Journal of Investigative Psychology and Offender Profiling, 2019)
This study compared the Stepwise Interview, Cognitive Interview, and Reality Interview in detecting deception with inmates. The dependent measures were the amount of unique details provided during the free narrative and mnemonics and the number of words provided during the free narrative and mnemonics of each interview. The Stepwise Interview generated 58.3% accuracy, the Cognitive Interview generated 70.0% accuracy, and the Reality Interview generated 93.3% accuracy. The different tasks of these interviews increased the differences between honest and deceptive statements and therefore, increased the accuracy in detection of deception. Differential recall enhancement is used to explain the findings.
Keywords: credibility assessment; dept.psy; detecting deception; investigative interviewing; peer-reviewed

Does eyewitness and interviewer gender influence children’s reports? An experimental analysis of eyewitness and interviewer gender on children’s testimony - Foster, Ida; Wyman, Joshua; Tong, Donia; Colwell, Kevin; Talwar, Victoria (Psychiatry, Psychology and Law, 2019)
This study examines how children's age, gender and interviewer gender affected children's testimony after witnessing a theft. Children (N=127, age = 6-11 years) witnessed an experimenter (E1) find money, which he/she may/may not have taken. E1 then asked the children to falsely deny that the theft occurred, falsely accuse E1 of taking the money, or tell the truth when interviewed by a second experimenter. Falsely denying or falsely accusing influenced children's forthcomingness and quality of their testimony. When accusing, boys were significantly more willing than girls to disclose about the theft earlier and without being asked directly. When truthfully accusing, children gave lengthier testimony to same-gendered adults. When denying, children were significantly more willing to disclose the theft earlier to male interviewers than to females. As children aged, they were significantly less likely to lie, more likely to disclose earlier when accusing, and give lengthier and more consistent testimony.
Keywords: adult; article; child; children; dept.psy; disclosures; false accusations; false denials; female; gender; girl; human; interviewer gender; lying; major clinical study; male; money; peer-reviewed; preschool child; theft; witness

Audiovisual speech perception in children with autism spectrum disorders - Irwin, Julia R.; Avery, T; Kleinman, D; Landi, N (ICA 2019 Aachen, 2019)
In face-to-face conversation, when a speaker talks, the outcome of their speech can both be heard (audio) and seen (visual). We employed a novel visual phonemic restoration paradigm to assess neural signatures (event related potentials [ERPs]) of audiovisual processing in typically developing children and in children with ASD. During EEG recording, two types of auditory stimuli were alternately presented with video of a speaker saying the consonant-vowel syllable /ba/: 1) a synthesized consonant-vowel syllable /ba/ or 2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant are substantially weakened, such that it sounds more like /a/. The auditory stimuli are easily discriminable, however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. In an ERP context, we have shown that this restoration leads to an attenuated phoneme discrimination response in an active task in typical adults and children. To explore the hypothesis that children with autism spectrum disorder (ASD) have atypical AV speech integration under pre-attentive processing conditions, we tested whether children with ASD would show a reduction in this restoration effect under passive listening conditions. Indeed, in this task, children with ASD showed a large /ba/-/a/ discrimination response, even in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2019 Proceedings of the International Congress on Acoustics. All rights reserved.
Keywords: Audiovisual; Autism; Phonemic Restoration; Speech; dept.psy

Personality and political preferences: the 2016 U.S. presidential election - Abe, Jo Ann A (Journal of Research in Personality, 2018)
This study examined whether personality variables would account for political preferences during the 2016 U.S. Presidential Election using a demographically diverse sample of participants (N = 897). Study A revealed participants' ratings of their own personality and emotions were weakly associated with political preferences, but their ratings of candidates' personality showed robust associations, and were far more predictive of voting intention than all of the demographic variables, political affiliation, and racial attitudes combined. In Study B, linguistic analysis of narratives revealed words reflective of liberal values were correlated with positive evaluations of Clinton's personality, whereas words reflective of conservative values and “populist” sentiment were correlated with positive evaluations of Trump's personality, suggesting appraisals of candidates may be associated with values. (C) 2018 Elsevier Inc. All rights reserved.
Keywords: Five Factor Model of Personality (FFM); Liberal and conservative values; Linguistic analysis; Political preferences; dept.psy; peer-reviewed; “Populist” sentiment

Personality, Well-Being, and Cognitive-Affective Styles: A Cross-Sectional Study of Adult Third Culture Kids - Abe, Jo Ann A. (Journal of Cross-Cultural Psychology, 2018)
Third Culture Kids (TCKs) and their adult counterparts (ATCKs) refer to individuals who spent part of their developmental years abroad and are an important demographic to study in this rapidly globalizing world. To date, the bulk of the research on (A)TCKs has been descriptive and little is known about their developmental trajectories in adulthood. The major objective of this study was to examine the personality traits, dimensions of well-being, and cognitive-affective styles of ATCKs across the adult life span using well-validated psychological measures. A subsidiary goal was to develop a new multidimensional international experiences scale to assess levels of multicultural engagement in ATCKs. The participants in this study (N = 700+; age = 18-80+) were recruited from the Alumni Office of an international school in Japan. Somewhat contrary to how they are often depicted in the news media and in qualitative studies, the ATCKs showed normative changes in personality and well-being in the direction of greater maturity and adjustment during adulthood, with those reporting higher levels of multicultural engagement generally exhibiting a more resilient personality profile, higher levels of well-being, and more adaptive cognitive and affective styles.
Keywords: adult third culture kids; dept.psy; five-factor model of personality; need for closure; peer-reviewed; well-being

Influence of prenatal pre-exposure to an odor on intake behavior of an aversive solution in newborn rats. - Kamenetzky, Giselle V; Suarez, Andrea B; Ifran, Maria Celeste; Nizhnikov, Michael E; Pautassi, Ricardo M (Neuroscience letters, 2018)
Early pre- or postnatal sensory experiences significantly influence flavor preference and food intake, and can induce liking for innately unpalatable flavors. Previous work found that newborn rats stimulated with an odor experienced shortly after birth exhibited heightened intake and seeking towards an artificial nipple containing quinine. This result suggests that odors made familiar trough early postnatal pre-exposure can shift the motivational value of unconditional stimuli. The objective of the current study was to assess the effect of an odor (lemon) experienced in-utero on the first intake responses towards an artificial nipple supplying quinine. The hypothesis, which was corroborated, was that stimulation with the olfactory stimulus experienced in-utero would increase the newborn's intake and grasp responses to the artificial nipple containing quinine. Exposure to the odor that had been pre-exposed in utero increased quinine intake and seeking (i.e., latency to grasp and total time in contact with the nipple, as well as number of and mean duration of nipple grasps) in 3-h-old pups. These results replicate those previously found with postnatal odor pre-exposure, and extend the phase for pre-exposure to the prenatal stage. Copyright © 2018 Elsevier B.V. All rights reserved.
Keywords: *Eating; *Feeding Behavior; *Odorants; *Prenatal Exposure Delayed Effects; *Quinine/ad [Administration & Dosage]; Animals; Animals, Newborn; Animals, Suckling; Article; Eating; Feeding Behavior; Female; Male; Neonate rat; Odor pre-exposure; Odorants; Pregnancy; Prenatal Exposure Delayed Effects; Prenatal exposure; Quinine; Rats, Sprague-Dawley; Smell; Sprague Dawley rat; animal; animal experiment; aversive agent; controlled study; dept.psy; eating; feeding behavior; female; food intake; fragrance; learning; male; newborn; nipple; nonhuman; odor; peer-reviewed; pregnancy; prenatal exposure; priority journal; quinine; rat; smelling; stimulation; suckling animal

Intentional multiple mating by females in a species where sneak fertilization circumvents female choice for parental males - Stiver, Kelly A.; Kindsvater, Holly K.; Tamburello, Natascia; Heckman, Kellie L.; Klein, Joanne; Alonzo, Suzanne H. (Journal of Fish Biology, 2018)
This paper describes how individual female ocellated wrasse Symphodus ocellatus distribute their spawning among males and nests in space and time. It is based on previously collected genetic data of larvae from ten different nests (used to reconstruct half and full-sibling groupings both within and among nests on multiple days) and behavioural data of marked females across the reproductive season. Both the genetic analyses and behavioural observations confirm that female S. ocellatus intentionally engage in multiple mating, by repeatedly spawning at the same nest on different days and at several different nests (up to 12 spawning events over 3 weeks), leading to mixed paternity among her young. The main benefit of such high and intentional multiple mating is probably insurance against brood failure due to nest predation, desertion or poor paternal care by the male. These findings reveal that even in systems where females attempt to avoid male-controlled mixed paternity, they may still engage in intentional multiple mating due to these potential benefits. © 2018 The Fisheries Society of the British Isles
Keywords: Animals; Female; Fertilization; Male; Mating Preference, Animal; Paternity; Perciformes; Reproduction; Sexual Behavior, Animal; Symphodus ocellatus; animal; behaviour; dept.psy; female; fertilization; male; mate choice; mating systems; paternity; peer-reviewed; reproduction; sexual behavior; sexual conflict; sexual selection; trade-offs

Substance use, anxiety, and depressive symptoms among college students - Walters, Kenneth S.; Bulmer, Sandra Minor; Troiano, Peter F.; Obiaka, Uzoma; Bonhomme, Rebecca (Journal of Child & Adolescent Substance Abuse, 2018)
Research on college substance use and mental illness is limited and inconsistent. Measures of substance use, and anxiety and depressive symptoms, were completed by 1,316 undergraduates within a major drug transportation corridor. Hierarchical linear regressions were used to test associations between anxious and depressive symptoms and substance use (i.e., alcohol, cannabis, tobacco, cocaine, other amphetamines, sedatives, hallucinogens, and designer drugs). Depressive symptoms were associated with use of cannabis, tobacco, amphetamines, cocaine, sedatives, and hallucinogens. Anxiety symptoms were unrelated to substance use. These findings support the need for education and prevention at universities, emphasizing tobacco, cannabis, and certain “harder” drugs.
Keywords: anxiety; college students; depression; dept.hhs; dept.psy; mental health; peer-reviewed; substance use

Electrophysiological Indices of Audiovisual Speech Perception: Beyond the McGurk Effect and Speech in Noise. - Irwin, Julia; Avery, Trey; Brancazio, Lawrence; Turcios, Jacqueline; Ryherd, Kayleigh; Landi, Nicole (Multisensory research, 2018)
Visual information on a talker's face can influence what a listener hears. Commonly used approaches to study this include mismatched audiovisual stimuli (e.g., McGurk type stimuli) or visual speech in auditory noise. In this paper we discuss potential limitations of these approaches and introduce a novel visual phonemic restoration method. This method always presents the same visual stimulus (e.g., /ba/) dubbed with a matched auditory stimulus (/ba/) or one that has weakened consonantal information and sounds more /a/-like). When this reduced auditory stimulus (or /a/) is dubbed with the visual /ba/, a visual influence will result in effectively 'restoring' the weakened auditory cues so that the stimulus is perceived as a /ba/. An oddball design in which participants are asked to detect the /a/ among a stream of more frequently occurring /ba/s while either a speaking face or face with no visual speech was used. In addition, the same paradigm was presented for a second contrast in which participants detected /pa/ among /ba/s, a contrast which should be unaltered by the presence of visual speech. Behavioral and some ERP findings reflect the expected phonemic restoration for the /ba/ vs. /a/ contrast; specifically, we observed reduced accuracy and P300 response in the presence of visual speech. Further, we report an unexpected finding of reduced accuracy and P300 response for both speech contrasts in the presence of visual speech, suggesting overall modulation of the auditory signal in the presence of visual speech. Consistent with this, we observed a mismatch negativity (MMN) effect for the /ba/ vs. /pa/ contrast only that was larger in absence of visual speech. We discuss the potential utility for this paradigm for listeners who cannot respond actively, such as infants and individuals with developmental disabilities.
Keywords: Audio-visual speech; Audio-visual stimulus; Audiovisual; Audiovisual speech perception; Auditory stimuli; Developmental disability; ERP; Electrophysiology; Enterprise resource planning; Mismatch negativity; Phonemic restoration; Potential utility; Restoration; Speech; Speech recognition; Visual information; dept.psy; peer-reviewed; phonemic restoration

A familiarization protocol facilitates the participation of children with asd in electrophysiological research - Turcios, Jacqueline; Cook, Barbara; Irwin, Julia; Rispoli, Taylor; Landi, Nicole (JoVE (Journal of Visualized Experiments), 2017)
This paper includes a detailed description of a familiarization protocol, which is used as an integral component of a larger research protocol to collect electroencephalography (EEG) data and Event-Related Potentials (ERPs). At present, the systems available for the collection of high-quality EEG/ERP data make significant demands on children with developmental disabilities, such as those with an Autism Spectrum Disorder (ASD). Children with ASD may have difficulty adapting to novel situations, tolerating uncomfortable sensory stimuli, and sitting quietly. This familiarization protocol uses Evidence-Based Practices (EBPs) to increase research participants' knowledge and understanding of the specific activities and steps of the research protocol. The tools in this familiarization protocol are a social narrative, a visual schedule, the Premack principle, role-playing, and modeling. The goal of this familiarization protocol is to increase understanding and agency and to potentially reduce anxiety for child participants, resulting in a greater likelihood of the successful completion of the research protocol for the collection of EEG/ERP data.
Keywords: dept.cmd; dept.psy

Personality, Emotional Qualities of Leisure, and Subjective Well-Being in the Elderly. - Kahlbaugh, Patricia; Huffman, Loreen (International journal of aging & human development, 2017)
In this study, we examined personality traits of older adults and their emotional experiences associated with engaging in specific leisure activities. Older individuals (17 males, 32 females), ages ranging from 65 to 97 years (mean age 74), completed measures of Big Five personality traits, positive and negative affect, subjective well-being (SWB), independent functioning, and an emotion-activity inventory. As expected, Extraversion, Agreeableness, Conscientiousness, and Openness to experience were related to positive affect, while Neuroticism was related to negative affect. Openness and Agreeableness were related to positive emotions experienced in social and cognitive domains, and Agreeableness was related to greater SWB, greater positive affect, and more positively experienced activities. Neuroticism was related to lower SWB and fewer positively experienced activities. These findings suggest that assessing the fit between personality and emotions experienced during activities should be considered when creating programs tailored to elderly individuals, with the goal of encouraging more active and rewarding lives.
Keywords: *Aging/px [Psychology]; *Emotions; *Leisure Activities; *Personal Satisfaction; *Personality; Affect; Aged; Aged, 80 and over; Aging; Emotions; Female; Humans; Leisure Activities; Male; Personal Satisfaction; Personality; affect; aged; aging; dept.psy; emotion; emotions; female; human; leisure; male; personality; psychology; satisfaction; subjective well-being; successful aging; very elderly

Restraint stress enhances alcohol intake in adolescent female rats but reduces alcohol intake in adolescent male and adult female rats. - Wille-Bille, Aranza; Ferreyra, Ana; Sciangula, Martina; Chiner, Florencia; Nizhnikov, Michael E; Pautassi, Ricardo Marcos (Behavioural brain research, 2017)
Adolescents may be more sensitive to stress-induced alcohol drinking than adults, which would explain the higher prevalence of alcohol abuse and dependence in late adolescence than in adulthood. The present study analyzed the impact of restraint stress on the initiation of alcohol intake across 2 weeks of intermittent, two-bottle choice intake in male and female adolescent rats and adult female rats. Restraint stress significantly increased alcohol intake and preference in female adolescent rats but decreased alcohol intake and preference in male adolescent and female adult rats. The effects of restraint stress on alcohol intake were mitigated in adolescent females following administration of the kappa opioid receptor antagonist norbinaltorphimine. Adolescent but not adult female rats that were subjected to restraint stress spent more time on the open arms of the elevated plus maze. Female adolescents exposed to stress also exhibited greater risk-taking behaviors in a concentric square field test compared with non-stressed controls. These results indicate age- and sex-related differences in the sensitivity to alcohol-stress interactions that may facilitate the initiation of alcohol use in female adolescents. The facilitatory effect of stress on alcohol intake was related to greater exploratory and risk-taking behaviors in young females after stress exposure. Copyright © 2017 Elsevier B.V. All rights reserved.
Keywords: *Aging/ph [Physiology]; *Aging/px [Psychology]; *Alcohol Drinking/pp [Physiopathology]; *Alcohol Drinking/px [Psychology]; *Sex Characteristics; *Stress, Psychological/pp [Physiopathology]; Adolescents; Adults; Age differences; Aging; Aging/de [Drug Effects]; Alcohol; Alcohol Drinking; Alcohol Drinking/dt [Drug Therapy]; Animals; Article; Central Nervous System Depressants; Central Nervous System Depressants/ad [Administration & Dosage]; Choice Behavior; Choice Behavior/de [Drug Effects]; Choice Behavior/ph [Physiology]; Disease Models, Animal; Ethanol; Ethanol/ad [Administration & Dosage]; Exploratory Behavior; Exploratory Behavior/de [Drug Effects]; Exploratory Behavior/ph [Physiology]; Female; Male; Motor Activity; Motor Activity/de [Drug Effects]; Motor Activity/ph [Physiology]; Naltrexone; Naltrexone/aa [Analogs & Derivatives]; Naltrexone/pd [Pharmacology]; Narcotic Antagonists; Narcotic Antagonists/pd [Pharmacology]; Rats, Wistar; Receptors, Opioid, kappa; Receptors, Opioid, kappa/ai [Antagonists & Inhibitors]; Receptors, Opioid, kappa/me [Metabolism]; Restraint, Physical; Risk-Taking; Sex Characteristics; Stress; Stress, Psychological; Stress, Psychological/dt [Drug Therapy]; Wistar rat; [kappa] opioid receptors; adolescent; adult; age; aging; alcohol; alcohol consumption; analogs and derivatives; animal; animal experiment; antagonists and inhibitors; behavior assessment; central depressant agent; comparative study; concentric square field test; controlled study; decision making; dept.psy; disease model; drinking behavior; drug effects; drug therapy; elevated plus maze test; exercise; experimental study; exploratory behavior; exploratory behavior test; female; high risk behavior; immobilization stress; kappa opiate receptor; kappa opiate receptor antagonist; male; mental stress; metabolism; motor activity; naltrexone; narcotic antagonist; nonhuman; norbinaltorphimine; pathophysiology; peer-reviewed; physiology; priority journal; psychology; rat; risk assessment; sensitivity analysis; sex difference; sexual characteristics; κ opioid receptors

Electrophysiological Indices of Audiovisual Speech Perception in the Broader Autism Phenotype. - Irwin, Julia; Avery, Trey; Turcios, Jacqueline; Brancazio, Lawrence; Cook, Barbara; Landi, Nicole (Brain sciences, 2017)
When a speaker talks, the consequences of this can both be heard (audio) and seen (visual). A novel visual phonemic restoration task was used to assess behavioral discrimination and neural signatures (event-related potentials, or ERP) of audiovisual processing in typically developing children with a range of social and communicative skills assessed using the social responsiveness scale, a measure of traits associated with autism. An auditory oddball design presented two types of stimuli to the listener, a clear exemplar of an auditory consonant-vowel syllable /ba/ (the more frequently occurring standard stimulus), and a syllable in which the auditory cues for the consonant were substantially weakened, creating a stimulus which is more like /a/ (the infrequently presented deviant stimulus). All speech tokens were paired with a face producing /ba/ or a face with a pixelated mouth containing motion but no visual speech. In this paradigm, the visual /ba/ should cause the auditory /a/ to be perceived as /ba/, creating an attenuated oddball response; in contrast, a pixelated video (without articulatory information) should not have this effect. Behaviorally, participants showed visual phonemic restoration (reduced accuracy in detecting deviant /a/) in the presence of a speaking face. In addition, ERPs were observed in both an early time window (N100) and a later time window (P300) that were sensitive to speech context (/ba/ or /a/) and modulated by face context (speaking face with visible articulation or with pixelated mouth). Specifically, the oddball responses for the N100 and P300 were attenuated in the presence of a face producing /ba/ relative to a pixelated face, representing a possible neural correlate of the phonemic restoration effect. Notably, those individuals with more traits associated with autism (yet still in the non-clinical range) had smaller P300 responses overall, regardless of face context, suggesting generally reduced phonemic discrimination.
Keywords: Article; Audiovisual speech perception; Broader autism phenotype; Development; ERP; audiovisual aid; audiovisual equipment; audiovisual speech perception; autism; behavior; broader autism phenotype; child; clinical article; dept.cmd; dept.hls; dept.psy; development; electrophysiology; female; human; male; participant observation; phenotype; social adaptation; social competence; speech perception; stimulus; vision test

Electrophysiology of perception and processing of phonological information as indices of toddlers' language performance - Harwood, Vanessa; Preston, Jonathan; Grela, Bernard; Roy, Dooti; Harold, Olivia; Turcios, Jacqueline; Andrada, Kiyomi; Landi, Nicole (Journal of Speech Language and Hearing Research, 2017)
Purpose: The toddler years are a critical period for language development and growth. We investigated how event-related potentials (ERPs) to repeated and novel nonwords are associated with clinical assessments of language in young children. In addition, nonword repetition (NWR) was used to measure phonological working memory to determine the unique and collective contribution of ERP measures of phonemic discrimination and NWR as predictors of language ability. Method: Forty children between the ages of 24-48 months participated in an ERP experiment to determine phonemic discrimination to repeated and novel nonwords in an old/new design. Participants also completed a NWR task to explore the contribution of phonological working memory in predicting language. Results: ERP analyses revealed that faster responses to novel stimuli correlated with higher language performance on clinical assessments of language. Regression analyses revealed that an earlier component was associated with lower level phonemic sensitivity, and a later component was indexing phonological working memory skills similar to NWR. Conclusion: Our findings suggest that passive ERP responses indexing phonological discrimination and phonological working memory are strongly related to behavioral measures of language.
Keywords: Brain; Child Language; Child, Preschool; Discrimination (Psychology); Electroencephalography; Evoked Potentials; Female; Humans; Language Tests; Male; Memory, Short-Term; Pattern Recognition, Physiological; Phonetics; Reaction Time; Regression Analysis; Signal Processing, Computer-Assisted; Speech Perception; adult; brain; child; clinical article; dept.psy; electroencephalography; event related potential; evoked response; female; human; language ability; language development; language test; male; pattern recognition; perception; perceptive discrimination; phonetics; physiology; preschool child; reaction time; regression analysis; short term memory; signal processing; speech perception; stimulus; working memory; young adult; ⚠️ Invalid DOI

EdPsych modules - Durwin, Cheryl Cisero; Reese-Weber, Marla J. (SAGE Publications, Inc, 2017)
Now with SAGE Publications, Cheryl Cisero Durwin and Marla Reese-Weber’s EdPsych Modules uses an innovative implementation of case studies and a modular format to address the challenge of effectively connecting theory and research to practice.  Each module is a succinct, stand-alone topic that represents every subject found in traditional chapter texts and can be used in any order for maximum flexibility in organizing your course.  Each of the book’s eight units of modules begins with a set of four case studies–early childhood, elementary, middle school, and secondary–and ends with "Assess" and "Reflect and Evaluate" questions and activities to encourage comprehension and application of the research and theories presented. The case approach and the extensive pedagogy that support it allows students to constantly see the applications of the theories and research that they are studying in the text.
Keywords: dept.psy

The development of gaze to a speaking face. - Irwin, Julia; Brancazio, Lawrence; Volpe, Nicole (The Journal of the Acoustical Society of America, 2017)
When a speaker talks, the visible consequences of what they are saying can be seen. Listeners are influenced by this visible speech both in a noisy listening environment and even when auditory speech can easily be heard. While visible influence on heard speech has been reported to increase from early to late childhood, little is known about the mechanism that underlies this developmental trend. One possible account of developmental differences is that looking behavior to the face of a speaker changes with age. To examine this possibility, the gaze to a speaking face was examined in children from 5 to 10 yrs of age and adults. Participants viewed a speaker's face in a range of conditions that elicit looking: in a visual only (speech reading) condition, in the presence of auditory noise (speech in noise) condition, and in an audiovisual mismatch (McGurk) condition. Results indicate an increase in gaze on the face, and specifically, to the mouth of a speaker between the ages of 5 and 10 for all conditions. This change in looking behavior may help account for previous findings in the literature showing that visual influence on heard speech increases with development.
Keywords: *Facial Expression; *Fixation, Ocular; *Speech Acoustics; *Speech Perception; *Visual Perception; *Voice Quality; Acoustic Stimulation; Acoustics; Age Factors; Audiometry, Speech; Child; Child, Preschool; Cues; Early-to-late; Facial Expression; Female; Fixation, Ocular; Humans; Male; Noise; Noise/ae [Adverse Effects]; Perceptual Masking; Photic Stimulation; Physics; Speech; Speech Acoustics; Speech Perception; Speech in noise; Speech reading; Video Recording; Visible speech; Visual Perception; Voice Quality; Young Adult; age; association; auditory stimulation; child; dept.hls; dept.psy; eye fixation; facial expression; female; human; male; masking; noise; photostimulation; preschool child; speech; speech audiometry; speech perception; videorecording; vision; voice; young adult

Strain-specific programming of prenatal ethanol exposure across generations. - Popoola, Daniel O; Nizhnikov, Michael E; Cameron, Nicole M (Alcohol (Fayetteville, N.Y.), 2017)
Behavioral consequences of prenatal alcohol exposure (PAE) can be transmitted from in utero-exposed F1 generation to their F2 offspring. This type of transmission is modulated by genetic and epigenetic mechanisms. This study investigated the intergenerational consequences of prenatal exposure to a low ethanol dose (1 g/kg) during gestational days 17-20, on ethanol-induced hypnosis in adolescent male F1 and F2 generations, in two strains of rats. Adolescent Long-Evans and Sprague-Dawley male rats were tested for sensitivity to ethanol-induced hypnosis at a 3.5-g/kg or 4.5-g/kg ethanol dose using the loss of righting reflex (LORR) paradigm. We hypothesized that PAE would attenuate sensitivity to ethanol-induced hypnosis in the ethanol-exposed animals in these two strains and in both generations. Interestingly, we only found this effect in Sprague-Dawley rats. Lastly, we investigated PAE related changes in expression of GABAA receptor alpha1, alpha4, and delta subunits in the cerebral cortex of the PAE sensitive Sprague-Dawley strain. We hypothesized a reduction in the cerebral cortex GABAA receptor subunits' expression in the F1 and F2 PAE groups compared to control animals. GABAA receptor alpha1, alpha4, and delta subunits protein expressions were quantified in the cerebral cortex of F1 and F2 male adolescents by western blotting. PAE did not alter cerebral cortical GABAA receptor subunit expressions in the F1 generation, but it decreased GABAA receptor alpha4 and delta subunits' expressions in the F2 generation, and had a tendency to decrease alpha1 subunit expression. We also found correlations between some of the subunits in both generations. These strain-dependent vulnerabilities to ethanol sensitivity, and intergenerational PAE-mediated changes in sensitivity to alcohol indicate that genetic and epigenetic factors interact to determine the outcomes of PAE animals and their offspring. Copyright © 2017 Elsevier Inc. All rights reserved.
Keywords: *Alcohol Drinking/ae [Adverse Effects]; *Behavior, Animal/de [Drug Effects]; *Cerebral Cortex/de [Drug Effects]; *Ethanol/to [Toxicity]; *Prenatal Exposure Delayed Effects; *Receptors, GABA-A/de [Drug Effects]; 4 aminobutyric acid A receptor; 4 aminobutyric acid A receptor alpha1; 4 aminobutyric acid A receptor alpha4; Age Factors; Alcohol Drinking; Alcohol Drinking/ge [Genetics]; Alcohol Drinking/me [Metabolism]; Alcohol Drinking/px [Psychology]; Animals; Article; Behavior, Animal; Blood Alcohol Content; Cerebral Cortex; Cerebral Cortex/me [Metabolism]; Cerebral Cortex/pa [Pathology]; Dose-Response Relationship, Drug; Epigenesis, Genetic; Epigenesis, Genetic/de [Drug Effects]; Ethanol; Ethanol/bl [Blood]; Female; Gestational Age; Long Evans rat; Male; Maternal Exposure; Pregnancy; Prenatal Exposure Delayed Effects; Rats, Long-Evans; Rats, Sprague-Dawley; Reaction Time; Receptors, GABA-A; Receptors, GABA-A/ge [Genetics]; Receptors, GABA-A/me [Metabolism]; Reflex, Righting; Reflex, Righting/de [Drug Effects]; Species Specificity; Sprague Dawley rat; Time Factors; Western blotting; adolescent; adult; age; alcohol; alcohol blood level; alcohol consumption; animal; animal behavior; animal experiment; animal model; animal tissue; blood; brain cortex; comparative study; controlled study; correlational study; dept.psy; dose response; drinking behavior; drug effects; epigenetics; female; genetic epigenesis; genetics; gestation period; gestational age; hemoglobin delta chain; heredity; hypnosis; male; maternal exposure; metabolism; nonhuman; outcome assessment; pathology; peer-reviewed; pregnancy; prenatal exposure; progeny; protein expression; psychology; rat; rat strain; reaction time; righting reflex; species difference; time factor

Audiovisual speech perception: A new approach and implications for clinical populations - Irwin, Julia; DiBlasi, Lori (Language and Linguistics Compass, 2017)
This selected overview of audiovisual (AV) speech perception examines the influence of visible articulatory information on what is heard. Thought to be a cross-cultural phenomenon that emerges early in typical language development, variables that influence AV speech perception include properties of the visual and the auditory signal, attentional demands, and individual differences. A brief review of the existing neurobiological evidence on how visual information influences heard speech indicates potential loci, timing, and facilitatory effects of AV over auditory only speech. The current literature on AV speech in certain clinical populations (individuals with an autism spectrum disorder, developmental language disorder, or hearing loss) reveals differences in processing that may inform interventions. Finally, a new method of assessing AV speech that does not require obvious cross-category mismatch or auditory noise was presented as a novel approach for investigators.
Keywords: dept.psy

Teaching and learning guide for audiovisual speech perception: A new approach and implications for clinical populations. - Irwin, Julia; Turcios, Jacqueline (Language and linguistics compass, 2017)
Keywords: dept.psy